Application of perovskite nanocrystals in the preparation of probes for tumor diagnosis or treatment
Water-soluble perovskite nanocrystal probes with liposome coatings address the limitations of traditional glioma detection by providing high fluorescence intensity and narrow emission, enabling rapid and accurate surgical guidance for glioma identification.
Patent Information
- Application Number
- CN202211379981.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-11-23
- Filing Date
- 2022-11-04
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-11-04
AI Technical Summary
Existing fluorescence imaging technologies for glioma detection suffer from poor fluorescence stability, low efficiency, and limited resolution, making it difficult to achieve accurate real-time detection during surgery.
Development of water-soluble perovskite nanocrystals coated with liposomes, such as DSPC-PEG-COOH, coupled with biomaterials like chlorotoxin, to form probes that provide high fluorescence intensity and narrow emission, enabling rapid imaging of glioma cells and tissues using a handheld UV lamp.
The method allows for rapid, sensitive, and intuitive detection of glioma cells and tissues, enhancing surgical guidance with high accuracy and simplicity, overcoming limitations of traditional imaging methods.
Smart Images

Figure CN115825442B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of immunoassay, and relates to an application of perovskite nanocrystals in preparing probes for tumor diagnosis or treatment, specifically a rapid pathological diagnosis method for brain glioma, including a method for rapid detection of brain glioma cells, tissue sections and rapid imaging of living tissues. Background Art
[0002] Gliomas are one of the most common diseases in the nervous system. Due to their easy invasion and metastatic spread, they show high recurrence and mortality rates. Multimodal imaging that combines intraoperative MRI imaging, near-infrared fluorescence imaging, and ultrasound is a common method for guiding tumor resection. MRI imaging can provide good resolution and accuracy, but does not provide real-time continuous guidance and is expensive; ultrasound is portable and low-cost, but has limited contrast and resolution in intraoperative imaging, making it difficult to detect accurately in real time. Therefore, fluorescence imaging has great advantages in detecting tumors during surgery. It can not only provide real-time imaging with high resolution and accuracy, but also provide real-time and direct visual guidance for tumor cells.
[0003] With the growing demand for rapid and real-time intraoperative tumor cell detection, the requirements for fluorescent biodetection probes are also getting higher and higher. Although many studies have used some traditional fluorescent substances to guide the resection of gliomas, the poor fluorescence stability and low fluorescence efficiency can no longer meet the detection requirements of high fluorescence efficiency, narrow emission, and low interference. Therefore, it is of great significance to develop a new type of nano-biodetection probe with high fluorescence intensity, narrow emission, and good biocompatibility.
[0004] Perovskite nanocrystal materials have become the fluorescent labeling materials with the highest quantum yield among existing materials due to the size effect and quantum confinement of the materials themselves. And perovskite nanocrystal materials also have the advantages of narrow emission peak (<20nm), controllable emission peak position, wide excitation wavelength range, and easy synthesis. However, perovskite quantum dots are not resistant to water and oxygen, which seriously restricts their application and development in many fields such as biological sciences and medicine. Therefore, how to modify perovskite quantum dots to construct a nanobiological probe that can give full play to the advantages of the material and has good biocompatibility is an urgent problem to be solved. Here, we propose a preparation method for water-soluble carboxyl-terminated polylactic acid-glycolic acid copolymer-coated perovskite quantum dots, which retains high quantum yield (PLQY=70%) while maintaining water and oxygen resistance (>200 days). The water-soluble perovskite nanocrystal can be coupled with chlorotoxin antibodies that specifically bind to receptors on the membrane of glioma cells through electrostatic interactions to form a perovskite nanocrystal probe with high fluorescence intensity in the aqueous phase. Because it can specifically identify glioma cells, it can distinguish between tumor tissue, adjacent cancer tissue and normal tissue, and can achieve real-time and direct visual guidance for tumor resection.
[0005] Gliomas are the neurosurgical diseases with the greatest and most direct impact on neurological function. Gliomas are highly invasive and adjacent to important neurological structures, making them difficult to remove accurately during surgery. Even with surgical and radiotherapy and chemotherapy treatments, the prognosis is still poor, and most glioma patients are prone to recurrence after comprehensive treatment. Therefore, how to quickly assist surgeons in achieving accurate resection of gliomas during surgery has become an important problem.
[0006] At present, intraoperative assisted glioma imaging mainly relies on imaging technologies such as MRI, CT, and fluorescence. Fluorescence imaging can not only provide real-time imaging with high resolution and high accuracy, but also provide real-time and direct visual guidance for tumor cells. In recent years, with the development of nanotechnology, different types of nanomaterials have been used as probes for fluorescence imaging. With the unique advantages of functionalized nanomaterials, fluorescence imaging has shown great advantages in the precise diagnosis and treatment of gliomas, showing broad prospects for clinical application.
[0007] With the increasing demand for biological detection, nanocomposite probes are showing a diversified development trend. Nano fluorescent probes can realize rapid identification of target substances, and therefore are very suitable for on-site real-time detection of target substances. The first generation of fluorescent labeling materials such as fluorescent pigments, fluorescein isothiocyanate, and rhodamine 6G all have high photoluminescence quantum yields, but the emission peak widths of the above fluorescent labeling materials are all over 50nm, which seriously limits their application in real-time detection of multi-target detection objects. The second generation of fluorescent labeling materials is quantum dots, which have advantages such as symmetrical and narrow emission peaks, large Stokes shifts, high quantum yields, and size-dependent emission spectra compared to traditional fluorescent molecules. And under the influence of quantum confinement, the emission peak position of quantum dots can be adjusted to the near-infrared light (NIR) region by changing the size and elemental composition of quantum dots. Based on the above excellent performance, quantum dots have an incomparable role in the field of biological applications compared with other traditional fluorescent labeling materials. At the same time, with the continuous development and progress of quantum dot synthesis methods, quantum dots can be combined with a variety of nanomaterials to further reduce the biological toxicity of quantum dots, and the detection method of biological small molecules based on quantum dots has attracted widespread attention, especially quantum dots based on heavy metal Cd. However, it is still difficult to obtain quantum dots with a peak width below 30nm using the above methods.
[0008] Perovskite nanocrystal materials have become the fluorescent labeling materials with the highest quantum yield among existing materials due to their own size effect and quantum confinement. Perovskite nanocrystal materials also have the advantages of narrow emission peak (<20nm), controllable emission peak position, wide excitation wavelength range, and easy synthesis. However, perovskite quantum dots are not resistant to water and oxygen, which seriously restricts their application and development in many fields such as biological sciences and medicine.
[0009] With the development of chemistry, materials science, biology and other fields, the research and application of nanobiotechnology has attracted the attention of more and more researchers, especially in the field of bioanalysis. Nanomaterials occupy an important position in the field of biological small molecule analysis due to their controllable morphology and size, modifiability of surface functional groups and unique optical properties. Compared with traditional detection probes, nanobiocomposite probes have many advantages such as multifunctional composite, multiple detection channels, easy signal amplification and simple preparation. It is particularly noteworthy that a variety of nanobioprobes have excellent optical properties, which can be used to realize biological detection using conventional optical equipment, and even naked eye detection.
[0010] Fluorescence immunoassay technology refers to the use of fluorescent substances to label antibodies or antigen molecules, and after specific binding with the analyte, report fluorescent signals to achieve qualitative or quantitative detection of the target analyte. Nanofluorescent probes have been widely studied in the fields of biological detection, sensing, and drug molecule recognition due to their high sensitivity, high specificity, and simple and low-cost detection instruments. With the growing demand for multi-target detection objects, the requirements for biological detection probes are also getting higher and higher. Traditional nanobioprobes can no longer meet the detection requirements of high fluorescence efficiency, narrow emission, and low interference. Therefore, it is of great significance to develop a new type of nanobiodetection probe with high fluorescence intensity, narrow emission, and good biocompatibility.
[0011] Compared with traditional fluorescent materials, perovskite quantum dot materials have advantages such as high quantum yield, narrow emission peak, large Stokes shift, and easy surface modification, and have become a hot research object. However, perovskite quantum dots are not resistant to water and oxygen, which limits their application in research fields such as biological sciences and medicine. Therefore, how to modify perovskite quantum dots to construct a nano-bioprobe that can give full play to the advantages of the material and has good biocompatibility is an urgent problem to be solved. Summary of the invention
[0012] The purpose of the present invention is to provide an application of perovskite nanocrystals in preparing probes for tumor diagnosis or treatment.
[0013] The perovskite nanocrystals in the application include perovskite quantum dots and liposome materials coated on the surface of the perovskite quantum dots.
[0014] The liposome coating material is preferably DPPC, DPPE, DSPC and derivatives thereof.
[0015] The liposome coating material is further preferably DSPC-PEG, DPPC-PEG, or DPPE-PEG.
[0016] The liposome coating material is most preferably DSPC-PEG-COOH.
[0017] The perovskite quantum dots mentioned above are preferably CsPbBr3 perovskite quantum dots.
[0018] The probe in the above application is a biological material labeled with perovskite nanocrystals; the biological material is one, two or more of antibodies, aptamers and polypeptides.
[0019] The tumor in the above application is preferably a brain glioma.
[0020] The biological material in the above application is preferably an antibody, aptamer or polypeptide that specifically recognizes brain glioma tissue.
[0021] The biological material is further preferably at least one of chlorotoxin, IDH isocitrate dehydrogenase I, glial fibrillary acid protein antibody, Anti-ATRX, and rabbit anti-human H3K27Me3 polyclonal antibody.
[0022] The spectral range of the water-soluble perovskite nanocrystals in the above application is preferably 470 to 650 nm.
[0023] The particle size of the water-soluble perovskite nanocrystals in the above application is preferably 100-200 nm.
[0024] The perovskite nanocrystals described in the above application are obtained by heating and stirring the liposome material and the perovskite quantum dots.
[0025] The purpose of the present invention is to provide a method for preparing a water-soluble perovskite nanocrystal probe and its application in brain glioma cell imaging.
[0026] The water-soluble perovskite quantum dot nanomaterial provided by the invention comprises perovskite quantum dots and carboxyl-terminated polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) coated on the surface of the perovskite quantum dots.
[0027] According to an embodiment of the present invention, the water-soluble nanomaterial is nanocrystal.
[0028] According to an embodiment of the present invention, the average particle size of the perovskite quantum dots is 5 to 20 nm, for example, 10 to 15 nm; illustratively, the average particle size of the quantum dots is 12 nm.
[0029] According to an embodiment of the present invention, the average particle size of the water-soluble perovskite nanomaterial is greater than the average particle size of the perovskite quantum dots, for example, 5 to 100 nm, preferably 10 to 80 nm, exemplarily, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm.
[0030] According to a specific embodiment of the present invention, the average particle size of the water-soluble perovskite nanomaterial is 70 nm.
[0031] According to an embodiment of the present invention, the coating may be complete coating.
[0032] According to an embodiment of the present invention, the water-soluble perovskite nanocrystal is composed of carboxyl-terminated polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) coated on CsPbBr 3 Perovskite quantum dots were prepared on the surface.
[0033] According to an embodiment of the present invention, the quantum dots may be perovskite quantum dots, carbon quantum dots, cadmium quantum dots, zinc sulfide quantum dots or sulfur quantum dots, and are preferably CsPbBr 3 Perovskite quantum dots.
[0034] According to an embodiment of the present invention, the CsPbBr 3 Perovskite quantum dots appear yellow under visible light and green under ultraviolet light (e.g., 365nm excitation).
[0035] According to an embodiment of the present invention, the number average molecular weight of the carboxyl-terminated polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) is 100-200000, preferably 110000. Preferably, the carboxyl-terminated polylactic acid-glycolic acid copolymer is randomly copolymerized with racemic lactide (DLLA) and glycolide (GA), and the ratio of racemic lactide (DLLA) to glycolide (GA) is (50-90): (10-50), preferably 90:10, 75:25, 80:20, 60:40, 50:50.
[0036] According to an exemplary embodiment of the present invention, the water-soluble quantum dot nanomaterial is the water-soluble perovskite nanomaterial, denoted as P-PQDs, which includes CsPbBr 3 Perovskite quantum dots and coated on the CsPbBr 3 Carboxyl-terminated poly(lactic-co-glycolic acid) (OH-PLGA-COOH) on the surface of perovskite quantum dots.
[0037] According to an embodiment of the present invention, the water-soluble quantum dot nanomaterial has almost the same optical properties as quantum dots; for example, P-PQDs have the same optical properties as CsPbBr 3 Perovskite quantum dots have almost identical optical properties.
[0038] In order to overcome the shortcomings of the existing fluorescence imaging technology, which is complex and has a long cycle, the present invention provides a rapid pathological diagnosis method for rapid detection of brain glioma cells, tissue sections and living tissues. The diagnostic method has the characteristics of high sensitivity, rapid detection, simplicity, and intuition. The diagnostic method uses water-soluble perovskite nanocrystal materials as fluorescent labels to quickly respond and identify tumor areas (including cells, tissue sections and living tissues), and judge the detection results under the irradiation of a simple handheld ultraviolet lamp, which greatly improves the efficiency of detecting tumor cells or tissues and has guiding significance in assisting tumor resection during clinical surgery.
[0039] The technical solution of the present invention is as follows:
[0040] This diagnostic method uses water-soluble perovskite nanocrystal materials as fluorescent labels, coupled with biological materials targeting gliomas, to form perovskite-based probes, which are used for rapid 10-minute imaging of gliomas at the cellular level, tissue sections, and living tissue levels, providing a clinical method for rapid pathological diagnosis during surgery to assist tumor resection.
[0041] The perovskite nanocrystalline material is an all-inorganic perovskite quantum dot (CsPbBr 3 ).
[0042] Wherein, the CsPbBr 3 Perovskite quantum dots appear light yellow under visible light and green under ultraviolet light (e.g., 365nm excitation).
[0043] The water-soluble perovskite nanocrystals include all-inorganic perovskite quantum dots (CsPbBr 3 ) and a liposome material coated on the surface of the perovskite quantum dots;
[0044] The biomaterial is selected from one, two or more of antibodies, aptamers and polypeptides targeting brain gliomas, such as chlorotoxin (CTX), IDH isocitrate dehydrogenase I (IDH-1), glial fibrillary acid protein antibody (GFAP), Anti-ATRX, rabbit anti-human H3K27Me3 polyclonal antibody, etc., preferably, chlorotoxin (CTX).
[0045] The liposome coating material is DPPC (dipalmitoylphosphatidylcholine), DPPE (dipalmitoylphosphatidylethanolamine), DSPC (distearylphosphatidylcholine) and other substances and their derivatives; for example: DSPC-PEG (distearylphosphatidylcholine polyethylene glycol), DPPC-PEG (dipalmitoylphosphatidylcholine polyethylene glycol), DPPE-PEG (dipalmitoylphosphatidylethanolamine polyethylene glycol), preferably with -COOH, -NH 2and -SH are DSPC-PEG-COOH (distearoylphosphatidylcholine polyethylene glycol modified with a carboxyl group at the terminal end).
[0046] According to an embodiment of the present invention, the spectral range of the water-soluble perovskite nanocrystal is 470-650 nm, for example, 480 nm, 520 nm, 580 nm, 650 nm, preferably, the spectral position of the water-soluble perovskite nanocrystal is 520 nm.
[0047] According to an embodiment of the present invention, the particle size of the water-soluble perovskite nanocrystal is 100-200 nm, for example, 100 nm, 150 nm or 200 nm. Preferably, the particle size of the water-soluble perovskite nanocrystal is 100 nm.
[0048] According to an embodiment of the present invention, the average particle size of the perovskite quantum dots is 5 to 20 nm, for example, 10 to 15 nm; illustratively, the average particle size of the perovskite quantum dots is 5 nm, 10 nm, 12 nm, or 15 nm.
[0049] According to an embodiment of the present invention, the mass ratio (mg:mg) of the perovskite quantum dots to the liposome material is 116:(25-50); for example, it can be 116:(25-40). For example, it can be 116:25, 116:30, 116:35, 116:40.
[0050] According to an embodiment of the present invention, the coating is complete coating. For example, when the mass ratio (mg:mg) of the perovskite quantum dots to DSPC-PEG-COOH (distearoylphosphatidylcholine polyethylene glycol with terminal carboxyl modification) is at least 116:25, complete coating can be achieved.
[0051] According to an embodiment of the present invention, the weight average molecular weight of the DSPC-PEG-COOH (distearoylphosphatidylcholine polyethylene glycol modified with a carboxyl group at the terminal) is 1000-20000, for example, 3400-20000, and for another example, 3400.
[0052] According to an embodiment of the present invention, the water-soluble perovskite nanocrystal includes CsPbBr 3 Perovskite quantum dots and coated on the CsPbBr 3 DSPC-PEG-COOH (distearoylphosphatidylcholine polyethylene glycol modified with carboxyl groups at the end) on the surface of perovskite quantum dots, denoted as D-PNCs.
[0053] According to an embodiment of the present invention, the water-soluble perovskite nanocrystals have almost the same optical properties as perovskite quantum dots; for example, D-PNCs have similar optical properties to CsPbBr 3Perovskite quantum dots have almost identical optical properties.
[0054] According to an embodiment of the present invention, the method for preparing the water-soluble perovskite nanocrystals comprises the following steps: heating and stirring the distearoylphosphatidylcholine polyethylene glycol with a carboxyl group modified at the end and the perovskite quantum dots to obtain the water-soluble perovskite nanocrystals.
[0055] According to an embodiment of the present invention, the method for preparing water-soluble perovskite nanocrystals specifically comprises the following steps:
[0056] (A1) mixing and dissolving the raw materials for preparing perovskite quantum dots and distearoylphosphatidylcholine polyethylene glycol with a terminal carboxyl group modified therewith in a solvent, and then adding an organic ligand to form a stable solution;
[0057] (A2) adding the stable solution in step (A1) into an anti-solvent, heating the reaction, and precipitating water-soluble perovskite nanocrystals by an anti-solvent supersaturation method to prepare water-soluble perovskite nanocrystals.
[0058] According to an embodiment of the present invention, the perovskite quantum dots are CsPbBr 3 When the perovskite quantum dots are prepared, the raw materials for preparing the perovskite quantum dots are, for example, CsBr and PbBr 2 .
[0059] Wherein, the CsPbBr 3 Perovskite quantum dots can be prepared by methods known in the art.
[0060] According to an embodiment of the present invention, in step (A1), there is no limitation on the mixing order of the raw materials for preparing perovskite quantum dots and the distearoylphosphatidylcholine polyethylene glycol with a terminal modified carboxyl group. For example, the raw materials for preparing perovskite quantum dots and the distearoylphosphatidylcholine polyethylene glycol with a terminal modified carboxyl group can be added to the solvent at the same time, or the raw materials for preparing perovskite quantum dots can be added to the solvent first, and then the distearoylphosphatidylcholine polyethylene glycol with a terminal modified carboxyl group is added to the solvent.
[0061] According to an embodiment of the present invention, in step (A1), the ratio (mg:mg) of the sum of the masses of the raw materials for preparing perovskite quantum dots to the mass of distearoylphosphatidylcholine polyethylene glycol (DSPC-PEG-COOH) modified with a carboxyl group at the end is 116:(25-50); for example, it can be 116:(25-40).
[0062] According to an embodiment of the present invention, in step (A1), the mass volume ratio of the terminal carboxyl-modified distearoylphosphatidylcholine polyethylene glycol to the solvent is (10-30) mg:1 mL, for example, 10 mg:1 mL, 15 mg:1 mL, 18 mg:1 mL, 20 mg:1 mL, 25 mg:1 mL or 30 mg:1 mL.
[0063] According to an embodiment of the present invention, in step (A1), the solvent may be selected from one or both of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).
[0064] According to an embodiment of the present invention, in step (A1), the organic ligand may be selected from at least one of oleic acid, oleylamine, octylamine and octanoic acid, for example, a mixture of oleic acid and oleylamine in any proportion.
[0065] Preferably, the volume ratio of the organic ligand to the solvent is (0.5-5):10, for example (1-3):10, exemplified by 0.5:10, 1:10, 1.5:10, 2:10, 2.5:10, 3:10, 4:10 or 5:10.
[0066] According to an embodiment of the present invention, step (A1) is synthesized in an all-air process.
[0067] According to an embodiment of the present invention, in step (A2), the anti-solvent is selected from at least one of toluene, chlorobenzene and n-hexane.
[0068] According to an embodiment of the present invention, step (A2) comprises: firstly dropping the stable solution described in step (A1) into an anti-solvent to obtain water-soluble perovskite nanocrystals; heating the reaction, and after the reaction is completed, collecting the precipitate by high-speed centrifugation, and ultrasonically dispersing it in water to obtain water-soluble perovskite nanocrystals.
[0069] Preferably, the volume ratio of the stabilizing solution to the anti-solvent is (0.1-5):10, for example (0.5-3):10.
[0070] Preferably, the dripping is slow dripping, for example, the dripping speed is 3 to 10 μL / s, exemplarily 3 μL / s, 5 μL / s, 10 μL / s.
[0071] Preferably, the dropwise addition is performed under the condition of vigorous stirring of the anti-solvent, for example, the stirring speed is 800 to 1000 r, exemplarily 800 r, 850 r, 900 r, 950 r, 1000 r.
[0072] Preferably, the water-soluble perovskite nanocrystal solution is added to an excess anti-solvent, heated and stirred to react, and the water-soluble perovskite nanocrystal is precipitated to obtain the water-soluble perovskite nanocrystal.
[0073] For example, the stirring time is 2-5h, such as 2h, 3h, 4h, 5h. For example, the reaction temperature is 40-60°C, such as 40-50°C, such as 30, 40°C, 45°C, 50°C, 60°C.
[0074] According to an embodiment of the present invention, the water-soluble perovskite nanocrystalline material can be excited by a handheld ultraviolet lamp to exhibit green fluorescence.
[0075] Furthermore, the wavelength range of the ultraviolet lamp is 320-450 nm, preferably 365 nm.
[0076] Furthermore, the power of the ultraviolet lamp is 10-50W, preferably 10W.
[0077] According to an embodiment of the present invention, the method for preparing a probe formed by coupling the water-soluble perovskite nanocrystal fluorescent material with a biomaterial targeting glioma comprises the following steps:
[0078] (1) Disperse water-soluble perovskite nanocrystals (D-PNCs) powder into ultrapure water (pH = 6.2-6.8) and disperse uniformly by ultrasonication.
[0079] (2) Add biological material to step (1) and mix, collect the fluorescent part, and prepare a probe solution.
[0080] According to an embodiment of the present invention, the detection probe is obtained by adjusting the pH of the solution to combine the perovskite nanocrystal material with a strong positive charge with the negatively charged biomaterial targeting brain glioma through electrostatic interaction.
[0081] According to an embodiment of the present invention, the probe is stored in a diluent; the diluent is ultrapure water containing 0.01 to 0.1 wt % Triton X-100. Exemplarily, the pH of the ultrapure water is 6.2 to 6.8.
[0082] According to an embodiment of the present invention, the obtained detection solution can also be stored in a refrigerator. For example, the storage temperature is 1 to 5°C, such as 1°C, 2°C, 3°C, 4°C or 5°C.
[0083] According to an embodiment of the present invention, in step (1), ultrasound is performed for 5-10 min, for example, 1 min, 2 min, 3 min, 4 min, 5 min, 8 min, 10 min.
[0084] As a preferred embodiment of the present invention, the method for preparing the probe comprises the following steps:
[0085] A. Dissolve D-PNCs (e.g., with a wavelength of 520 nm) in ultrapure water and perform ultrasonic treatment for 5 min to make them uniformly dispersed in the solvent.
[0086] B. Add antibody (e.g., the antibody is chlorotoxin CTX), shake on a 37°C incubator, and react for 10 min.
[0087] C. After the reaction is completed, use an ultrafiltration centrifuge tube with a molecular cutoff of 30-100KDa to concentrate to 30-100ul, then use the gel size exclusion method to purify the concentrate, collect the fluorescent part, and then concentrate it with an ultrafiltration centrifuge tube and store it in a diluent (containing 0.05% Triton X-100), and store it at 4°C for use, and the probe solution is obtained.
[0088] The present invention also provides the application of the above-mentioned rapid diagnosis method for brain glioma in the fields of medical detection, medical diagnosis and treatment, and preferably, for detecting brain glioma cells, tissue sections and living tissue imaging.
[0089] The present invention also provides a specific step of the above-mentioned diagnostic method:
[0090] Take the above probe solution and add it dropwise to the substance to be detected for reaction, then use a handheld ultraviolet lamp to irradiate and observe whether fluorescence appears on the target substance to be detected.
[0091] According to an embodiment of the present invention, the amount of probe added is 100-300 μL.
[0092] According to an embodiment of the present invention, the reaction temperature is room temperature; the reaction time is 5 to 15 minutes, and illustratively, the reaction time is 10 minutes.
[0093] According to an embodiment of the present invention, after the reaction is completed, a flushing liquid may be used to flush the target substance to be detected; the flushing liquid is ultrapure water or physiological saline.
[0094] According to an embodiment of the present invention, the wavelength of the ultraviolet light is 320-450 nm.
[0095] As a preferred embodiment of the present invention, the method of use is, for example: take 200 μL of the above detection solution and drop it on the target substance to be detected, react at room temperature for 10 minutes, rinse with the post-reaction rinse solution 5-6 times, and observe with a handheld ultraviolet lamp for imaging.
[0096] According to an embodiment of the present invention, the target detection substance may be a brain glioma cell, a frozen section during a brain glioma sectioning operation, a paraffin section, and a living tissue removed during a brain glioma sectioning operation.
[0097] The evaluation standard of the diagnostic method of the present invention is: using an ordinary handheld ultraviolet lamp with a light source range of 320-450nm to excite water-soluble perovskite nanocrystals to irradiate the tissue area, according to the antibody-antigen specific recognition principle, when the target substance to be detected contains relevant antigens of the brain glioma tissue area, the detection solution is added dropwise to the tissue area, and after reacting for 10 minutes, the detection solution is rinsed 5-6 times with a rinse solution, and fluorescence appears in the tumor area under the excitation and irradiation of the handheld ultraviolet lamp, and the detection result is a brain glioma tumor area; conversely, the target substance to be detected is normal tissue, that is, it does not contain relevant antigens of the brain glioma area, and there is no fluorescence in the tumor area under the excitation and irradiation of the handheld ultraviolet lamp, and the detection result is a normal tissue area, that is, a non-tumor area.
[0098] The higher the fluorescence intensity, the higher the degree of glioma canceration in the tissue section to be tested. Conversely, the lower the fluorescence intensity, the lower the degree of canceration.
[0099] The present invention also provides a method for preparing the above-mentioned water-soluble perovskite quantum dot nanomaterial, comprising the following steps: coating the surface of the perovskite quantum dots with a carboxyl-terminated polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) to obtain the water-soluble perovskite quantum dot nanomaterial.
[0100] According to an embodiment of the present invention, the method for preparing the water-soluble perovskite quantum dot nanomaterial comprises the following steps:
[0101] (A1) mixing the raw materials for preparing quantum dots and the carboxyl-terminated poly(lactic acid-glycolic acid) copolymer in a solvent, and after the mixture is completely dissolved, adding a ligand material to form a stable solution;
[0102] (A2) adding the above-mentioned stable solution to an anti-solvent, precipitating the water-soluble perovskite nanocrystalline material by an anti-solvent supersaturation method, collecting the precipitate by high-speed centrifugation, and performing ultrasonic dispersion in water to obtain a water-soluble perovskite nanocrystalline material.
[0103] According to an embodiment of the present invention, in step (A1), the perovskite quantum dots have the meaning as described above. Depending on the perovskite quantum dots used, the raw materials for preparation can be selected. For example, CsPbBr 3 The raw materials for the preparation of perovskite quantum dots are CsBr and PbBr 2 .
[0104] The perovskite quantum dots can be prepared by methods known in the art.
[0105] According to an embodiment of the present invention, in step (A1), there is no limitation on the mixing order of the raw materials for preparing quantum dots and the carboxyl-terminated polylactic acid-glycolic acid copolymer. For example, the raw materials for preparing quantum dots and the carboxyl-terminated polylactic acid-glycolic acid copolymer can be added to the solvent at the same time, or the raw materials for preparing quantum dots can be added to the solvent first, and then the carboxyl-terminated polylactic acid-glycolic acid copolymer is added to the solvent.
[0106] According to an embodiment of the present invention, in step (A1), the molar ratio or molar mass ratio of the perovskite quantum dots to the carboxyl-terminated poly(lactic acid-glycolic acid) copolymer (OH-PLGA-COOH) is 1 mol:(300-600) mg, for example, 0.2 mol:90 mg.
[0107] According to an embodiment of the present invention, in step (A1), the mass volume ratio of the carboxyl-terminated polylactic acid-glycolic acid copolymer to the solvent is (5-30) mg:1 mL, for example, 90 mg:5 mL.
[0108] According to an embodiment of the present invention, in step (A1), the solvent may be selected from one or both of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).
[0109] According to an embodiment of the present invention, in step (A1), the ligand material may be selected from oleic acid, oleylamine and / or octylamine, preferably oleic acid and oleylamine.
[0110] Preferably, the volume ratio of the added amount of the ligand material to the solvent is (0.5-5):10, such as (1-3):10, and exemplified by 0.75:5.
[0111] According to an embodiment of the present invention, step (A1) is carried out under anhydrous and oxygen-free conditions, preferably in an inert atmosphere, such as nitrogen.
[0112] According to an embodiment of the present invention, in step (A2), the anti-solvent is selected from at least one of toluene, chlorobenzene and n-hexane.
[0113] According to an embodiment of the present invention, step (A2) comprises: firstly dropping the stabilizing solution into an anti-solvent to obtain a water-soluble perovskite quantum dot nanomaterial solution; collecting the precipitate by high-speed centrifugation, and performing ultrasonic dispersion in water to obtain a water-soluble perovskite nanocrystalline material. Preferably, the volume ratio of the stabilizing solution to the anti-solvent is (0.1-5):10, for example (0.5-3):10.
[0114] Preferably, the dripping is performed slowly drop by drop.
[0115] Preferably, the dropwise addition is performed under the condition of vigorous stirring of the anti-solvent.
[0116] Preferably, the volume ratio of the water-soluble perovskite quantum dot nanomaterial solution to the anti-solvent is (0.5-3):15, for example (1-2.5):15.
[0117] Preferably, the water-soluble perovskite quantum dot nanomaterial solution is added to an excess anti-solvent, heated and stirred to react, and the water-soluble perovskite quantum dot nanomaterial is precipitated. For example, the stirring reaction time is 5-10 hours, such as 5 hours, 7 hours, 8 hours, 10 hours. For example, the stirring reaction temperature is 30 to 60°C, such as 40 to 50°C, such as 30, 40°C, 42°C, 45°C, 48°C, 50°C, 60°C.
[0118] According to an embodiment of the present invention, the method for preparing the water-soluble perovskite quantum dot nanomaterial further comprises step (A3), separating the precipitated water-soluble perovskite quantum dot nanomaterial from the solution system, and drying to obtain a solid water-soluble perovskite nanocrystalline material.
[0119] According to an embodiment of the present invention, the method for preparing the water-soluble perovskite quantum dot nanomaterial further comprises a step (A4), wherein the solid water-soluble perovskite quantum dot nanomaterial obtained in step (A3) is dispersed in water to obtain a water-soluble perovskite nanocrystal solution.
[0120] The present invention also provides a water-soluble perovskite nanocrystal solution prepared by the above method.
[0121] The present invention also provides the use of the water-soluble quantum dot perovskite nanomaterial in a medical diagnostic probe or a kit. For example, the medical diagnostic probe may be a fluorescent biological detection probe or a cell imaging probe.
[0122] The present invention also provides a nanoprobe, which comprises the water-soluble quantum dot nanomaterial.
[0123] The present invention belongs to the fields of materials science and biomedicine, and relates to a water-soluble perovskite nanocrystal probe and a preparation method thereof and an application in brain glioma cell imaging, and specifically relates to a perovskite nanocrystal probe that can exist stably in a water system for a long time and a preparation method thereof and an application in brain glioma cell imaging.
[0124] According to an embodiment of the present invention, the nanoprobe is a biological material labeled by the water-soluble quantum dot nanomaterial, and is formed by coupling the water-soluble quantum dot perovskite nanomaterial with the biological material.
[0125] According to an embodiment of the present invention, the biomaterial can be selected from one, two or more of antibodies, aptamers, polypeptides, etc., preferably polypeptides. Exemplarily, the biomaterial is a polypeptide; for example, a chlorotoxin polypeptide.
[0126] According to an embodiment of the present invention, the nanoprobe can generate strong fluorescence in the range of 500 to 540 nm and generate the strongest emission at 515 ± 5 nm under excitation at 365 ± 5 nm.
[0127] According to an exemplary embodiment of the present invention, the nanoprobe is a chlorotoxin polypeptide labeled with a water-soluble perovskite nanomaterial P-PQDs, and is formed by the electrostatic interaction between P-PQDs and the chlorotoxin polypeptide.
[0128] According to an embodiment of the present invention, the mass ratio of the water-soluble quantum dot nanomaterial to the biomaterial is (10-50):1, preferably 20:1.
[0129] According to an embodiment of the present invention, the average particle size of the nanoprobes is between 20 and 100 nm, preferably 50 nm.
[0130] The present invention also provides a method for preparing the nanoprobe, which comprises coupling water-soluble perovskite nanocrystals and biomaterials to form the nanoprobe.
[0131] According to an embodiment of the present invention, the preparation method comprises the following steps: directly mixing a water-soluble perovskite nanocrystalline material with a biological material to obtain the nanoprobe through strong charge difference electrostatic interaction;
[0132] The water-soluble perovskite nanocrystalline material and biomaterial have the meanings as described above.
[0133] According to an embodiment of the present invention, the solvent in the cross-linking reaction agent solution is an ultrapure aqueous solution (eg, pH=6.42).
[0134] According to an embodiment of the present invention, the mass ratio of the biomaterial to the water-soluble quantum dot perovskite nanomaterial is 1:(10-50), for example, 1:20.
[0135] According to an embodiment of the present invention, step (B2) further comprises refrigerating the obtained nanoprobes. For example, the refrigerated storage temperature is 1-5°C, such as 1°C, 2°C, 3°C, 4°C, 5°C.
[0136] The present invention also provides a nanoprobe prepared by the method.
[0137] The present invention also provides a kit, which comprises the nanoprobe.
[0138] The present invention also provides the use of the above-mentioned water-soluble perovskite quantum dot nanomaterial, nanoprobe or kit in the fields of medical detection, medical diagnosis and treatment, etc. Preferably, the medical detection can be cell imaging or biological detection.
[0139] According to an embodiment of the present invention, the nanoprobe or kit can specifically recognize the following target analytes: antibodies, aptamers, polypeptides, antigens, target molecules, proteases, etc. For example, polypeptides, such as chlorotoxin polypeptides, etc.
[0140] The present invention also provides a method for using the nanoprobe or kit to specifically identify the target analyte, the method comprising: contacting the nanoprobe with the target analyte and identifying the target analyte through fluorescence detection.
[0141] A rapid diagnostic method for detecting brain gliomas, comprising a detection probe, wherein the detection solution contains a nanocrystal probe, and the nanocrystal probe is a biological material labeled with a water-soluble perovskite nanocrystal;
[0142] The water-soluble perovskite nanocrystals include perovskite quantum dots and DSPC-PEG-COOH (distearoylphosphatidylcholine polyethylene glycol with terminal carboxyl modified) coated on the surface of the perovskite quantum dots;
[0143] The biological material is selected from one, two or more of antibodies, aptamers and polypeptides.
[0144] The nanoprobe and the water-soluble perovskite nanocrystal have a spectral range of 470 to 650 nm.
[0145] Preferably, the particle size of the water-soluble perovskite nanocrystal is 100-200 nm.
[0146] The fluorescent marker, the perovskite quantum dot is CsPbBr 3 Perovskite quantum dots.
[0147] Preferably, the weight average molecular weight of the DSPC-PEG-COOH (distearoylphosphatidylcholine polyethylene glycol modified with a carboxyl group at the terminal) is 1,000-20,000.
[0148] The detection probe, the water-soluble perovskite nanocrystal includes CsPbBr 3 Perovskite quantum dots and coated on the CsPbBr 3 DSPC-PEG-COOH (distearoylphosphatidylcholine polyethylene glycol modified with carboxyl groups at the end) on the surface of perovskite quantum dots.
[0149] The detection probe and the preparation method of the water-soluble perovskite nanocrystal include: heating and stirring DSPC-PEG-COOH (distearoylphosphatidylcholine polyethylene glycol with terminal carboxyl modified) and perovskite quantum dots to react to obtain the water-soluble perovskite nanocrystal.
[0150] The nanoprobe and the method for preparing the water-soluble perovskite nanocrystal specifically comprise the following steps:
[0151] (A1) mixing and dissolving the raw materials for preparing perovskite quantum dots and DSPC-PEG-COOH (distearoylphosphatidylcholine polyethylene glycol with a terminal carboxyl group modified) in a solvent, and then adding an organic ligand to form a stable solution;
[0152] (A2) adding the stable solution in step (A1) into an anti-solvent, heating the reaction, and precipitating water-soluble perovskite nanocrystals by an anti-solvent supersaturation method to prepare water-soluble perovskite nanocrystals.
[0153] The portable visualization observation device is a handheld ultraviolet lamp.
[0154] Preferably, the wavelength range of the ultraviolet lamp is 320-450 nm.
[0155] Preferably, the power of the ultraviolet lamp is 10-50W.
[0156] Preferably, the biomaterial is an antibody, aptamer or polypeptide that specifically recognizes brain glioma tissue; and is at least one of chlorotoxin (CTX), IDH isocitrate dehydrogenase I (IDH-1), glial fibrillary acidic protein antibody (GFAP), Anti-ATRX, and rabbit anti-human H3K27Me3 polyclonal antibody.
[0157] The nanoprobe combines the perovskite nanocrystal material with a strong positive charge and the biomaterial with a negative charge targeting glioma through electrostatic action by regulating the pH of the solution. The preparation method of the detection nanoprobe includes the following steps:
[0158] (1) Disperse water-soluble perovskite nanocrystals (D-PNCs) powder into ultrapure water (pH = 6.2-6.8) and disperse uniformly by ultrasonication.
[0159] (2) Add biological material to step (1) and mix, collect the fluorescent part, and prepare a probe solution.
[0160] A rapid diagnostic method for brain glioma, applied to rapid 10-minute imaging of brain glioma cells, tissue sections and living tissues.
[0161] Beneficial effects of the present invention:
[0162] 1. The present invention utilizes polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) to treat CsPbBr 3 Perovskite quantum dots are encapsulated to prepare water-soluble perovskite nanocrystalline materials, and the optical properties of perovskite quantum dots are almost completely retained. ;
[0163] 2. The product of the present invention uses degradable polylactic acid to coat quantum dot materials to construct biological nanoprobes, which not only retains the high fluorescence intensity and narrow emission of quantum dots, but also gives them good biocompatibility, non-toxicity, and environmental protection. ;
[0164] 3. Since perovskite quantum dots have a narrow emission peak (<20nm), the water-soluble quantum dot nanocrystal bio-nanoprobe of the present invention can be used in the medical field for simultaneous detection of multiple analytes, and can avoid false negative results caused by crossover of fluorescent emission peaks, improve detection reliability, have universality and can achieve simultaneous detection of multiple target detection objects, greatly meet the needs of modern biotechnology and medical detection, and have important significance in the field of medical diagnosis and treatment. ;
[0165] 4. Water-soluble perovskite nanocrystals can be quickly and easily connected to biomaterials by electrostatic interaction through a simple strong potential difference, eliminating the need for cumbersome coupling reactions and the use of coupling kits. It is low-cost, simple to operate, and easy to commercialize. ;
[0166] 5. The invention provides a novel biological nanoprobe based on water-soluble perovskite quantum dot materials. Taking the chlorotoxin nanoprobe as an example, it can specifically identify glioma cells, thereby distinguishing tumor tissue, adjacent tissue and normal tissue, and can achieve real-time and direct visual guidance of tumor resection.
[0167] The invention uses the high quantum yield of a water-soluble perovskite-based nanoprobe to achieve rapid and highly sensitive 10-min imaging at the level of brain glioma cells, tissue slices, and living tissues, and a handheld ultraviolet lamp can be used for visual observation.
[0168] The rapid diagnostic method for brain glioma of the present invention specifically combines antibodies and antigens, and can be used for high-sensitivity rapid detection of brain glioma tissues or cells.
[0169] The labeling method of the present invention has the advantages of good labeling stability (for example, using biomolecules to covalently bind to perovskite nanocrystals), rapid and high sensitivity (for example, the fluorescence intensity of perovskite nanocrystals is high, which can detect low-concentration target molecules), simple and rapid operation, short detection time, easy result interpretation, and both qualitative and quantitative analysis. It is particularly suitable for doctors to guide clinical applications during surgery to remove brain gliomas.
[0170] In order to improve the above technical problems, the present invention provides a hydrophobic perovskite nanocrystal, comprising perovskite quantum dots and a polymer outer layer coated on the surface of the perovskite quantum dots, wherein the polymer in the polymer outer layer is a hydrophobic polymer containing terminal carboxyl groups.
[0171] According to an embodiment of the present invention, the hydrophobic polymer containing terminal carboxyl groups includes at least one of terminal carboxyl group-containing lactic acid-glycolic acid copolymers (OH-PLGA-COOH); preferably, in the lactic acid-glycolic acid copolymer, the ratio of racemic lactide (DLLA) to glycolide (GA) can be (50-90):(10-50), exemplified by 90:10, 85:15, 80:20, 75:25, 60:40, 50:50; for example, the ratio of racemic lactide DLLA to glycolide GA is 50:50.
[0172] According to an embodiment of the present invention, the number average molecular weight of the hydrophobic polymer containing terminal carboxyl groups is 1000-100000, preferably 5000-80000, and exemplified by 1000, 2000, 5000, 10000, 30000, 50000, 80000, and 100000.
[0173] According to an embodiment of the present invention, the chemical formula of the perovskite quantum dot is ABX 3 ;in:
[0174] A represents at least one of a methylamine cation, a formamidinium cation, a lithium ion, a sodium ion, a potassium ion, a rubidium (Rb) ion, and a cesium (Cs) ion; preferably a Cs ion;
[0175] B represents at least one of lead (Pb) ions, tin (Sn) ions, cadmium (Cd) ions, manganese (Mn) ions, zinc (Zn) ions and nickel (Ni) ions; preferably Pb ions;
[0176] X represents a monovalent anion; for example, a halogen ion, exemplified by at least one selected from the group consisting of a F ion, a Cl ion, a Br ion, and an I ion; preferably a Br ion.
[0177] According to an embodiment of the present invention, the particle size of the perovskite quantum dots is 10 to 20 nm, exemplified by 10 nm, 15 nm, and 20 nm.
[0178] According to an embodiment of the present invention, the chemical formula of the perovskite quantum dot is CsPbX 3 ; wherein X represents at least one of F, Cl, Br, I; preferably Br.
[0179] According to an embodiment of the present invention, the mass ratio of the perovskite quantum dots and the hydrophobic polymer containing terminal carboxyl groups is (40-70):(30-60), preferably (50-60):(40-50), and exemplified by 40:60, 50:50, 55:45, 60:40, and 70:30.
[0180] According to an embodiment of the present invention, the particle size of the hydrophobic perovskite nanocrystal is 40 to 90 nm, preferably 40 to 70 nm, and exemplified by 40 nm, 50 nm, 60 nm, 70 nm, and 80 nm.
[0181] The present invention also provides a method for preparing the hydrophobic perovskite nanocrystal, comprising coating a hydrophobic polymer containing terminal carboxyl groups on the surface of perovskite quantum dots to obtain the hydrophobic perovskite nanocrystal.
[0182] According to an embodiment of the present invention, the preparation method specifically comprises:
[0183] Prepare perovskite quantum dots by reacting raw materials including source A and source B, and then mix a hydrophobic polymer containing terminal carboxyl groups with the perovskite quantum dots to obtain the hydrophobic perovskite nanocrystals;
[0184] Alternatively, a hydrophobic polymer containing a terminal carboxyl group is mixed with raw materials including source A and source B, and reacted to obtain the hydrophobic perovskite nanocrystal.
[0185] According to an embodiment of the present invention, the preparation method specifically comprises the following steps:
[0186] (1) dissolving the A source, the B source and the hydrophobic polymer containing a terminal carboxyl group in a first solvent in sequence, and then adding a stabilizer to the mixed solution;
[0187] (2) Adding the mixed solution into a second solvent (such as toluene, chlorobenzene, cyclohexane, or n-hexane) to obtain the hydrophobic perovskite nanocrystal solution.
[0188] According to an embodiment of the present invention, the A source is provided by a compound containing A, and the A is selected from at least one of methylamine cations, formamidine cations, lithium ions, sodium ions, potassium ions, rubidium (Rb) ions and cesium (Cs) ions.
[0189] Preferably, the compound containing A may be at least one of bromide, chloride, fluoride and iodide containing A. More preferably, it is a bromide containing A.
[0190] According to an embodiment of the present invention, the B source is provided by a compound containing B, and the B is selected from at least one of lead (Pb) ions, tin (Sn) ions, cadmium (Cd) ions, manganese (Mn) ions, zinc (Zn) ions and nickel (Ni) ions.
[0191] Preferably, the compound containing B may be at least one of bromide, chloride, fluoride and iodide containing B. More preferably, it is a bromide containing B.
[0192] According to an embodiment of the present invention, the reaction is carried out in the presence of an A source, a B source, a stabilizer and a first solvent.
[0193] According to an embodiment of the present invention, the usage ratio of the A source, the B source and the hydrophobic polymer containing a terminal carboxyl group is (0.1-0.5) mmol: (0.1-0.5) mmol: 90 mg, preferably (0.2-0.4) mmol: (0.2-0.4) mmol: 90 mg, and exemplified by 0.1 mmol: 0.1 mmol: 90 mg, 0.2 mmol: 0.2 mmol: 90 mg, 0.3 mmol: 0.3 mmol: 90 mg, 0.4 mmol: 0.4 mmol: 90 mg, and 0.5 mmol: 0.5 mmol: 90 mg.
[0194] According to an embodiment of the present invention, the dosage ratio of the hydrophobic polymer containing terminal carboxyl groups and the stabilizer is 90 mg: (0.2-1.5) mL, preferably 90 mg: (0.2-1) mL, and exemplified by 90 mg: 0.2 mL, 90 mg: 0.5 mL, 90 mg: 0.75 mL, 90 mg: 1.0 mL, and 90 mg: 1.5 mL.
[0195] According to an embodiment of the present invention, the usage ratio of the hydrophobic polymer containing terminal carboxyl groups to the first solvent is 90 mg: (2-15) mL, preferably 90 mg: (3-10) mL, exemplified by 90 mg: 2 mL, 90 mg: 3 mL, 90 mg: 5 mL, 90 mg: 8 mL, 90 mg: 10 mL.
[0196] Preferably, the stabilizer is selected from oleic acid and / or oleylamine. More preferably, when the stabilizer is selected from two of oleic acid and oleylamine, the volume ratio of oleic acid to oleylamine is 1:(0.1-1), exemplified by 1:0.1, 1:0.5, 1:1, and preferably 1:0.5.
[0197] Preferably, the first solvent is at least one of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), preferably N,N-dimethylformamide (DMF).
[0198] Preferably, in step (2), the mixed solution is added to the second solvent in a dropwise manner. Preferably, the volume ratio of the mixed solution to the second solvent is 1:(5-30), exemplified by 1:5, 1:10, 1:15, 1:20, 1:25, 1:30.
[0199] Preferably, the preparation method further comprises:
[0200] (3) Adding the hydrophobic perovskite nanocrystal solution to a second solvent (such as toluene, chlorobenzene, cyclohexane, or n-hexane) again. Preferably, the volume ratio of the hydrophobic perovskite nanocrystal solution to the second solvent is 1:(5-25), exemplified by 1:5, 1:10, 1:15, 1:20, or 1:25.
[0201] Preferably, the preparation method is carried out under stirring conditions. For example, the stirring time is no more than 50 hours, preferably 4 to 48 hours, and exemplified by 4 hours, 12 hours, 16 hours, 24 hours, 30 hours, 36 hours, 40 hours, and 48 hours.
[0202] Preferably, the preparation method further comprises:
[0203] (4) performing solid-liquid separation on the hydrophobic perovskite nanocrystal solution. For example, the solid-liquid separation can be performed by means known in the art, such as centrifugation. Preferably, the centrifugal speed is 6000-12000rpm, for example, 7000-10000rpm, exemplified by 6000rpm, 7000rpm, 8000rpm, 9000rpm, 10000rpm. Further, the centrifugal time is 3-10min, for example, 5-8min, exemplified by 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min.
[0204] According to an embodiment of the present invention, the step (4) further comprises: drying the reaction product obtained by solid-liquid separation. For example, the drying temperature is 60 to 90°C, preferably 70 to 80°C, and exemplarily 60°C, 70°C, 80°C, and 90°C. Further, the drying time is 1 to 12 hours, preferably 1 to 10 hours, and exemplarily 1 hour, 4 hours, 8 hours, 10 hours, and 12 hours.
[0205] According to an embodiment of the present invention, the preparation method further comprises:
[0206] (5) dispersing the dried product in water to obtain a perovskite nanocrystal aqueous dispersion. Preferably, the process further comprises the step of ultrasonically treating the perovskite nanocrystal aqueous dispersion. For example, the ultrasonic treatment time is 1 to 10 minutes, preferably 2 to 8 minutes, and exemplarily 1 minute, 2 minutes, 5 minutes, 8 minutes, and 10 minutes.
[0207] According to an exemplary embodiment of the present invention, the method for preparing the hydrophobic perovskite nanocrystal comprises the following steps:
[0208] (1) CsBr, PbBr 2and polylactic acid-co-glycolic acid (OH-PLGA-COOH) containing terminal carboxyl groups are dissolved in N,N-dimethylformamide (DMF) solvent, and after being completely dissolved, oleic acid and oleylamine are added to stabilize the solution;
[0209] (2) Under stirring conditions, take the above solution and add it dropwise to the toluene solution to obtain CsPbBr 3 -QDs@PLGA perovskite nanocrystal solution;
[0210] (3) Take 1 mL of the solution obtained in step (2) and add it to the toluene solution. Stir the reaction until the coating is complete to obtain CsPbBr 3 -QDs@PLGA perovskite nanocrystals;
[0211] (4) CsPbBr prepared in step (3) 3 -QDs@PLGA perovskite nanocrystal solution was centrifuged and dried;
[0212] (5) Dispersing the product obtained in step (4) in water and ultrasonicating to obtain a uniformly dispersed CsPbBr 3 -QDs@PLGA perovskite nanocrystal aqueous dispersion.
[0213] The present invention also provides the application of the hydrophobic perovskite nanocrystals in fluorescent biological detection, for example, in constructing aqueous fluorescent biological detection probes.
[0214] The present invention also provides a fluorescent biological detection probe, which comprises the above-mentioned hydrophobic perovskite nanocrystal.
[0215] Beneficial effects of the present invention:
[0216] (1) The present invention is the first to use a hydrophobic polymer containing a terminal carboxyl group (e.g., poly(lactic acid-co-glycolic acid) copolymer (PLGA-COOH)) to achieve a simple, green anti-solvent "one-step" method for the hydrophobic reaction of perovskite quantum dots (e.g., CsPbBr 3 The perovskite quantum dots are coated with water to achieve the stable existence of the perovskite quantum dots in the aqueous phase, and the optical properties of the perovskite quantum dots are almost completely retained.
[0217] (2) The hydrophobic perovskite nanocrystal product prepared by the present invention can be used to prepare fluorescent groups with different emission wavelength ranges by adjusting the elemental composition of the perovskite quantum dots.
[0218] (3) The product of the present invention uses a degradable polymer (such as a polylactic acid polymer) as a coating material, which is green and environmentally friendly, has good biocompatibility, is simple to operate, and has low cost, and can be used for the mass preparation of perovskite nanocrystals.
[0219] (4) Specifically, the present invention uses polylactic acid-co-glycolic acid copolymer (PLGA-COOH) to treat CsPbBr 3 Perovskite quantum dots are coated with polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) containing terminal carboxyl groups, which is a very potential drug delivery carrier. It has the advantages of high drug encapsulation rate, strong modifiability, and good biosafety, so it can be used for the protection of biomaterials.
[0220] (5) The coating layer of the hydrophobic perovskite nanocrystalline material prepared by the present invention can expose a large number of active functional groups such as -COOH, which can provide reactive sites for the later coupling of biomaterials to construct biological probes, and can react with 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) to achieve coupling labeling of perovskite quantum dots with biomaterials through a simple, green coupling reaction of carboxyl and amino groups, so as to construct a new type of bioluminescent detection probe.
[0221] A hydrophobic perovskite nanocrystal comprises a perovskite quantum dot and a polymer outer layer coated on the surface of the perovskite quantum dot, wherein the polymer in the polymer outer layer is a hydrophobic polymer containing a terminal carboxyl group.
[0222] The hydrophobic perovskite nanocrystals, the hydrophobic polymer containing terminal carboxyl groups includes at least one of lactic acid-glycolic acid copolymers containing terminal carboxyl groups;
[0223] Preferably, in the lactic acid-glycolic acid copolymer, the ratio of racemic lactide (DLLA) to glycolide (GA) may be (50-90):(10-50), exemplified by 90:10, 85:15, 80:20, 75:25, 60:40, 50:50.
[0224] Preferably, the number average molecular weight of the hydrophobic polymer containing terminal carboxyl groups is 1,000 to 100,000, preferably 5,000 to 80,000.
[0225] The hydrophobic perovskite nanocrystal and the perovskite quantum dot have a chemical formula of ABX 3 ;in:
[0226] A represents at least one of a methylamine cation, a formamidinium cation, a lithium ion, a sodium ion, a potassium ion, a rubidium (Rb) ion, and a cesium (Cs) ion; preferably a Cs ion;
[0227] B represents at least one of lead (Pb) ions, tin (Sn) ions, cadmium (Cd) ions, manganese (Mn) ions, zinc (Zn) ions and nickel (Ni) ions; preferably Pb ions;
[0228] X represents a monovalent anion; for example, a halogen ion, exemplified by at least one selected from the group consisting of a F ion, a Cl ion, a Br ion, and an I ion; preferably a Br ion.
[0229] Preferably, the particle size of the perovskite quantum dots is 10 to 20 nm.
[0230] Preferably, the chemical formula of the perovskite quantum dot is CsPbX 3 ; wherein X represents at least one of F, Cl, Br, I; preferably Br.
[0231] The hydrophobic perovskite nanocrystals are characterized in that the mass ratio of the perovskite quantum dots to the hydrophobic polymer containing terminal carboxyl groups is (40-70):(30-60), preferably (50-60):(40-50).
[0232] Preferably, the particle size of the hydrophobic perovskite nanocrystals is 40 to 90 nm, preferably 40 to 70 nm.
[0233] The method for preparing the hydrophobic perovskite nanocrystal comprises coating a hydrophobic polymer containing terminal carboxyl groups on the surface of perovskite quantum dots to prepare the hydrophobic perovskite nanocrystal.
[0234] Preferably, the preparation method specifically comprises:
[0235] Prepare perovskite quantum dots by reacting raw materials including source A and source B, and then mix a hydrophobic polymer containing terminal carboxyl groups with the perovskite quantum dots to obtain the hydrophobic perovskite nanocrystals;
[0236] Alternatively, a hydrophobic polymer containing a terminal carboxyl group is mixed with raw materials including source A and source B, and reacted to obtain the hydrophobic perovskite nanocrystal.
[0237] The preparation method comprises the following steps:
[0238] (1) dissolving the A source, the B source and the hydrophobic polymer containing a terminal carboxyl group in a first solvent in sequence, and then adding a stabilizer to the mixed solution;
[0239] (2) Adding the mixed solution into a second solvent (such as toluene, chlorobenzene, cyclohexane, or n-hexane) to obtain the hydrophobic perovskite nanocrystal solution.
[0240] Preferably, the A source is provided by a compound containing A, and the A is selected from at least one of methylamine cations, formamidine cations, lithium ions, sodium ions, potassium ions, rubidium (Rb) ions and cesium (Cs) ions.
[0241] Preferably, the compound containing A may be at least one of bromide, chloride, fluoride and iodide containing A. More preferably, it is a bromide containing A.
[0242] Preferably, the B source is provided by a compound containing B, and the B is selected from at least one of lead (Pb) ions, tin (Sn) ions, cadmium (Cd) ions, manganese (Mn) ions, zinc (Zn) ions and nickel (Ni) ions.
[0243] Preferably, the compound containing B may be at least one of bromide, chloride, fluoride and iodide containing B. More preferably, it is a bromide containing B.
[0244] In the preparation method, the reaction is carried out in the presence of source A, source B, a stabilizer and a first solvent.
[0245] Preferably, the usage ratio of the A source, the B source and the hydrophobic polymer containing terminal carboxyl groups is (0.1-0.5) mmol: (0.1-0.5) mmol: 90 mg, preferably (0.2-0.4) mmol: (0.2-0.4) mmol: 90 mg.
[0246] Preferably, the usage ratio of the hydrophobic polymer containing terminal carboxyl groups to the stabilizer is 90 mg: (0.2-1.5) mL, preferably 90 mg: (0.2-1) mL.
[0247] Preferably, the usage ratio of the hydrophobic polymer containing terminal carboxyl groups to the first solvent is 90 mg:(2-15) mL, preferably 90 mg:(3-10) mL.
[0248] Preferably, the stabilizer is selected from oleic acid and / or oleylamine. More preferably, when the stabilizer is selected from two of oleic acid and oleylamine, the volume ratio of oleic acid to oleylamine is 1:(0.1-1).
[0249] Preferably, the first solvent is at least one of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), preferably N,N-dimethylformamide (DMF).
[0250] Preferably, in step (2), the mixed solution is added to the second solvent in a dropwise manner. Preferably, the volume ratio of the mixed solution to the second solvent is 1:(5-30).
[0251] Preferably, the preparation method further comprises:
[0252] (3) Adding the hydrophobic perovskite nanocrystal solution into a second solvent (such as toluene, chlorobenzene, cyclohexane, or n-hexane) again. Preferably, the volume ratio of the hydrophobic perovskite nanocrystal solution to the second solvent is 1:(5-25).
[0253] Preferably, the preparation method is carried out under stirring conditions. For example, the stirring time is no more than 50 hours, preferably 4 to 48 hours.
[0254] Preferably, the preparation method further comprises:
[0255] (4) performing solid-liquid separation on the hydrophobic perovskite nanocrystal solution. For example, the solid-liquid separation may be performed by means known in the art, such as centrifugation. Preferably, the centrifugal speed is 6000 to 12000 rpm, such as 7000 to 10000 rpm. Furthermore, the centrifugal time is 3 to 10 minutes, such as 5 to 8 minutes.
[0256] Preferably, step (4) further comprises: drying the reaction product obtained by solid-liquid separation. For example, the drying temperature is 60 to 90° C., preferably 70 to 80° C. Further, the drying time is 1 to 12 hours, preferably 1 to 10 hours.
[0257] Preferably, the preparation method further comprises
[0258] (5) dispersing the dried product in water to obtain a perovskite nanocrystal aqueous dispersion. Preferably, the process further comprises subjecting the perovskite nanocrystal aqueous dispersion to ultrasonic treatment. For example, the ultrasonic treatment time is 1 to 10 minutes, preferably 2 to 8 minutes.
[0259] The preparation method, the preparation method of the hydrophobic perovskite nanocrystal, comprises the following steps:
[0260] (1) CsBr, PbBr 2 and polylactic acid-co-glycolic acid (OH-PLGA-COOH) containing terminal carboxyl groups are dissolved in N,N-dimethylformamide (DMF) solvent, and after being completely dissolved, oleic acid and oleylamine are added to stabilize the solution;
[0261] (2) Under stirring conditions, take the above solution and add it dropwise to the toluene solution to obtain CsPbBr 3 -QDs@PLGA perovskite nanocrystal solution;
[0262] (3) Take 1 mL of the solution obtained in step (2) and add it to the toluene solution. Stir the reaction until the coating is complete to obtain CsPbBr 3 -QDs@PLGA perovskite nanocrystals;
[0263] (4) CsPbBr prepared in step (3) 3 -QDs@PLGA perovskite nanocrystal solution was centrifuged and dried;
[0264] (5) Dispersing the product obtained in step (4) in water and ultrasonicating to obtain a uniformly dispersed CsPbBr 3 -QDs@PLGA perovskite nanocrystal dispersion.
[0265] The hydrophobic perovskite nanocrystals and / or the hydrophobic perovskite nanocrystals prepared by the preparation method are used in fluorescent biological detection, for example, in constructing aqueous fluorescent biological detection probes.
[0266] A fluorescent biological detection probe comprises the hydrophobic perovskite nanocrystal and / or the hydrophobic perovskite nanocrystal prepared by the preparation method.
[0267] The invention provides a hydrophobic quantum dot nano material, a nano probe of the nano material, and preparation methods and applications of the two.
[0268] The hydrophobic quantum dot nanomaterial provided by the invention comprises quantum dots and carboxyl-terminated polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) coated on the surface of the quantum dots.
[0269] According to an embodiment of the present invention, the hydrophobic quantum dot nanomaterial is a nanocrystal.
[0270] According to an embodiment of the present invention, the average particle size of the quantum dots is 5 to 20 nm, for example, 10 to 15 nm; illustratively, the average particle size of the quantum dots is 12 nm.
[0271] According to an embodiment of the present invention, the average particle size of the hydrophobic quantum dot nanomaterial is larger than the average particle size of the quantum dots, for example 5 to 100 nm, preferably 10 to 80 nm, exemplarily 10 nm, 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm.
[0272] According to a specific embodiment of the present invention, the average particle size of the hydrophobic quantum dot nanomaterial is 80 nm.
[0273] According to an embodiment of the present invention, the coating is complete coating.
[0274] According to an embodiment of the present invention, the hydrophobic quantum dot nanomaterial is prepared by coating the surface of quantum dots with carboxyl-terminated poly(lactic acid-glycolic acid) copolymer (OH-PLGA-COOH).
[0275] According to an embodiment of the present invention, the quantum dots can be selected from modified or unmodified quantum dots as shown below: perovskite quantum dots, carbon quantum dots, cadmium quantum dots or sulfur quantum dots, etc., preferably modified or unmodified perovskite quantum dots. Wherein, the modification refers to the modification of the quantum dots with a fluorescent group pair (such as sulfydryl). Exemplarily, the quantum dots can be CsPbBr 3 Perovskite quantum dots or Sulfydryl-PQDs Perovskite quantum dots.
[0276] According to an embodiment of the present invention, the CsPbBr 3 Perovskite quantum dots appear pale yellow under visible light and green under ultraviolet light (e.g., 365nm excitation).
[0277] According to an exemplary embodiment of the present invention, the Sulfydryl-PQDs perovskite quantum dots appear cyan under visible light and appear blue under ultraviolet light (eg, 365 nm excitation).
[0278] According to an embodiment of the present invention, the number average molecular weight of the carboxyl-terminated polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) is 100 to 100,000, preferably 30,000. Preferably, the carboxyl-terminated polylactic acid-glycolic acid copolymer is synthesized by random copolymerization of racemic lactide (DLLA) and glycolide (GA), and the percentage of racemic lactide (DLLA) to glycolide (GA) is (50 to 90): (10 to 50), preferably 90:10, 75:25, 80:20, 60:40, 50:50.
[0279] According to an exemplary embodiment of the present invention, the hydrophobic quantum dot nanomaterial is a hydrophobic perovskite nanomaterial, denoted as PQDs@PLGA, which includes CsPbBr 3 Perovskite quantum dots and coated on the CsPbBr 3 Carboxyl-terminated poly(lactic-co-glycolic acid) (OH-PLGA-COOH) on the surface of perovskite quantum dots.
[0280] According to an embodiment of the present invention, the hydrophobic quantum dot nanomaterial has almost the same optical properties as quantum dots; for example, PQDs@PLGA has the same optical properties as CsPbBr 3 Perovskite quantum dots have almost identical optical properties.
[0281] The present invention also provides a method for preparing the hydrophobic quantum dot nanomaterial, comprising the following steps: coating the surface of the quantum dots with carboxyl-terminated polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) to obtain the hydrophobic quantum dot nanomaterial.
[0282] According to an embodiment of the present invention, the method for preparing the hydrophobic quantum dot nanomaterial comprises the following steps:
[0283] (A1) mixing the raw materials for preparing quantum dots and the carboxyl-terminated poly(lactic acid-glycolic acid) copolymer in a solvent, and after the mixture is completely dissolved, adding a ligand material to form a stable solution;
[0284] (A2) adding the above stable solution into an anti-solvent to form a hydrophobic quantum dot nanomaterial solution, and then precipitating the hydrophobic quantum dot nanomaterial using an anti-solvent supersaturation method.
[0285] According to an embodiment of the present invention, in step (A1), the quantum dots have the meanings as described above. Depending on the quantum dots used, the raw materials for preparation can be selected. For example, CsPbBr 3 The raw materials for the preparation of perovskite quantum dots include CsBr and PbBr 2 .
[0286] The quantum dots can be prepared by methods known in the art.
[0287] According to an embodiment of the present invention, in step (A1), there is no limitation on the mixing order of the raw materials for preparing quantum dots and the carboxyl-terminated polylactic acid-glycolic acid copolymer. For example, the raw materials for preparing quantum dots and the carboxyl-terminated polylactic acid-glycolic acid copolymer can be added to the solvent at the same time, or the raw materials for preparing quantum dots can be added to the solvent first, and then the carboxyl-terminated polylactic acid-glycolic acid copolymer is added to the solvent.
[0288] According to an embodiment of the present invention, in step (A1), the molar mass ratio of the quantum dots to the carboxyl-terminated poly(lactic acid-glycolic acid) copolymer (OH-PLGA-COOH) is 1 mmol:(300-600) mg, for example, 0.2 mmol:90 mg.
[0289] According to an embodiment of the present invention, in step (A1), the mass volume ratio of the carboxyl-terminated polylactic acid-glycolic acid copolymer to the solvent is (5-30) mg:1 mL, for example, 90 mg:5 mL.
[0290] According to an embodiment of the present invention, in step (A1), the solvent may be selected from one or both of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).
[0291] According to an embodiment of the present invention, in step (A1), the ligand material can be selected from oleic acid, oleylamine and / or sulfydryl, preferably oleic acid and oleylamine, or oleic acid, oleylamine and sulfydryl.
[0292] Preferably, the volume ratio of the added amount of the ligand material to the solvent is (0.5-5):10, such as (1-3):10, and exemplified by 0.75:5.
[0293] According to an embodiment of the present invention, step (A1) is carried out under anhydrous and oxygen-free conditions, preferably in an inert atmosphere, such as nitrogen.
[0294] According to an embodiment of the present invention, in step (A2), the anti-solvent is selected from at least one of toluene, chlorobenzene and n-hexane.
[0295] According to an embodiment of the present invention, step (A2) comprises: firstly dropping the stable solution into an anti-solvent to obtain a hydrophobic quantum dot nanomaterial solution; and then adding the hydrophobic quantum dot nanomaterial solution into an excess of anti-solvent to precipitate the hydrophobic quantum dot nanomaterial.
[0296] Preferably, the volume ratio of the stabilizing solution to the anti-solvent is (0.1-5):10, for example (0.5-3):10.
[0297] Preferably, the dripping is slow dripping.
[0298] Preferably, the dropwise addition is performed under the condition of vigorous stirring of the anti-solvent.
[0299] Preferably, the volume ratio of the hydrophobic quantum dot nanomaterial solution to the anti-solvent is (0.5-3):15, for example (1-2.5):15.
[0300] Preferably, the hydrophobic quantum dot nanomaterial solution is added to an excess anti-solvent, heated and stirred to react, and the hydrophobic quantum dot nanomaterial is precipitated. For example, the stirring reaction time is 20 to 60 hours, such as 30 hours, 40 hours, 48 hours, 50 hours. For example, the stirring reaction temperature is 30 to 60°C, such as 40 to 50°C, such as 30°C, 40°C, 42°C, 45°C, 48°C, 50°C, 60°C.
[0301] According to an embodiment of the present invention, the method for preparing the hydrophobic quantum dot nanomaterial further comprises step (A3), separating the precipitated hydrophobic quantum dot nanomaterial from the solution system, and drying to obtain a solid hydrophobic quantum dot nanomaterial.
[0302] According to an embodiment of the present invention, the method for preparing the hydrophobic quantum dot nanomaterial further comprises a step (A4), dispersing the solid hydrophobic quantum dot nanomaterial obtained in step (A3) in water to obtain an aqueous dispersion of the hydrophobic quantum dot nanomaterial.
[0303] The present invention also provides a hydrophobic quantum dot nano material prepared by the method.
[0304] The present invention also provides the use of the hydrophobic quantum dot nanomaterial in a medical diagnostic probe or a kit. For example, the medical diagnostic probe may be a fluorescent biological detection probe or a cell imaging probe.
[0305] The present invention also provides a nanoprobe, which comprises the hydrophobic quantum dot nanomaterial.
[0306] According to an embodiment of the present invention, the nanoprobe is a biological material labeled with the hydrophobic quantum dot nanomaterial, and is formed by coupling the hydrophobic quantum dot nanomaterial with the biological material.
[0307] According to an embodiment of the present invention, the biomaterial can be selected from one, two or more of antibodies, aptamers, polypeptides, etc., preferably antibodies. Exemplarily, the antibody is an IgG antibody; for example, a human IgG antibody.
[0308] According to an embodiment of the present invention, the nanoprobe can generate strong fluorescence in the range of 500 to 540 nm and generate the strongest emission at 515 ± 5 nm under excitation at 365 ± 5 nm.
[0309] According to an exemplary embodiment of the present invention, the nanoprobe is a human IgG antibody labeled with a hydrophobic perovskite nanomaterial PQDs@PLGA, which is formed by coupling PQDs@PLGA with a human IgG antibody.
[0310] According to an embodiment of the present invention, the mass ratio of the hydrophobic quantum dot nanomaterial to the biomaterial is (10-50):1, preferably 20:1.
[0311] According to an embodiment of the present invention, the average particle size of the nanoprobes is between 100 and 500 nm, preferably 200 nm.
[0312] The present invention also provides a method for preparing the nanoprobe, which comprises coupling a hydrophobic quantum dot nanomaterial and a biological material to form the nanoprobe.
[0313] According to an embodiment of the present invention, the preparation method comprises the following steps: dispersing a hydrophobic quantum dot nanomaterial in a cross-linking reactant solution, adding a biomaterial and a surfactant thereto, to obtain the nanoprobe;
[0314] The hydrophobic quantum dot nanomaterials and biomaterials have the meanings as described above.
[0315] According to an embodiment of the present invention, the method for preparing the nanoprobe comprises the following steps:
[0316] (B1) dispersing a hydrophobic quantum dot nanomaterial in a cross-linking reagent solution and stirring to activate the carboxyl groups on the surface of the hydrophobic quantum dot nanomaterial;
[0317] (B2) adding biological material and surfactant to the solution obtained in step (B1) to obtain the nanoprobe.
[0318] According to an embodiment of the present invention, the cross-linking reagent is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS); preferably, the mass ratio of EDC to NHS is 1:(3-10), for example 1:5.
[0319] According to an embodiment of the present invention, the solvent in the cross-linking reagent solution is PBS buffer (eg, PBS buffer with pH=7.3).
[0320] According to a specific embodiment of the present invention, the cross-linking reagent solution is a mixture of EDC and NHS; for example, a 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) solution and an N-hydroxysuccinimide (NHS) solution can be prepared separately, and the two solutions are mixed to obtain a mixture of EDC and NHS. Preferably, the mixture of EDC and NHS is used as prepared.
[0321] According to a specific embodiment of the present invention, the mass concentration of the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) solution is 6 mg / mL; the mass concentration of the N-hydroxysuccinimide (NHS) solution is 30 mg / mL. Preferably, when the two solutions are mixed, the volume ratio of the EDC solution to the NHS solution is 1:1.
[0322] According to an embodiment of the present invention, the mass ratio of the biomaterial to the cross-linking reagent is (5-15):1, for example, 15:1, 14:1, 13:1, 12:1, 11:1, 10:1, 9:1, 8:1, 7:1, 6:1, 5:1.
[0323] According to an embodiment of the present invention, in order to fully activate the carboxyl groups on the surface of the hydrophobic quantum dot nanomaterial, magnetic stirring is required at room temperature during dispersion. For example, the stirring time is 10 to 60 minutes, such as 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, and 60 minutes.
[0324] According to an embodiment of the present invention, the addition of the surfactant can avoid the agglomeration of the hydrophobic quantum dot nanomaterial. Preferably, the surfactant is a nonionic surfactant, such as one, two or three of Triton X-100, alkyl polyglycoside APG, and fatty alcohol polyoxyethylene ether AEO.
[0325] According to an embodiment of the present invention, the mass volume ratio of the biomaterial to the surfactant is 1 mg: (0.1-1) μL.
[0326] According to an embodiment of the present invention, the mass ratio of the biomaterial to the hydrophobic quantum dot nanomaterial is 1:(10-50), for example, 1:20.
[0327] According to an embodiment of the present invention, in step (B2), when the biological material and the surfactant are added to the solution obtained in step (B1), a gentle reaction on a shaking table is required; preferably, the time for the gentle reaction on the shaking table is 10 to 60 minutes, for example, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or 60 minutes.
[0328] According to an embodiment of the present invention, step (B2) further comprises refrigerating the obtained nanoprobes. For example, the refrigerated storage temperature is 1-5°C, such as 1°C, 2°C, 3°C, 4°C, 5°C.
[0329] The present invention also provides a nanoprobe prepared by the method.
[0330] The present invention also provides a kit, which comprises the nanoprobe.
[0331] The present invention also provides the use of the hydrophobic quantum dot nanomaterial, nanoprobe or kit in the fields of medical detection, medical diagnosis and treatment, etc. Preferably, the medical detection can be cell imaging or biological detection.
[0332] According to an embodiment of the present invention, the nanoprobe or kit can specifically recognize the following target analytes: antibodies, aptamers, polypeptides, antigens, target molecules, proteases, etc. For example, antibodies, such as human IgG antibodies, etc. For example, antigens, such as goat anti-human IgG, rabbit anti-human IgG, mouse anti-human IgG, etc.
[0333] The present invention also provides a method for using the nanoprobe or kit to specifically identify the target analyte, the method comprising: contacting the nanoprobe with the target analyte and identifying the target analyte through fluorescence detection.
[0334] According to an embodiment of the present invention, the method comprises the following steps:
[0335] (S1) coating a well plate with a target analyte or a target analyte labeled with an element, and washing the well plate coated with the target analyte or the target analyte labeled with an element after incubation;
[0336] (S2) sealing and washing the coated well plate obtained in step (S1);
[0337] (S3) adding the nanoprobe to the closed coated well plate obtained in step (S2), contacting with the target analyte, washing, and identifying the target analyte through fluorescence detection.
[0338] According to an embodiment of the present invention, the target analyte has the meaning as described above. Exemplarily, the target analyte is an antigen, such as Eu-labeled anti-human IgG.
[0339] According to an embodiment of the present invention, the cleaning method is: using PBST (PBS buffer, pH=7.3, containing 0.5 volume concentration of Tween-20) for cleaning. Preferably, the number of cleaning times is 3 to 5 times.
[0340] According to an embodiment of the present invention, in step (S1), the element used to label the target analyte is Eu.
[0341] According to an embodiment of the present invention, the well plate is a 96-well plate.
[0342] According to an embodiment of the present invention, in step (S1), the incubation is performed on a well plate, such as a 96-well plate.
[0343] According to an embodiment of the present invention, the incubation is low temperature overnight incubation. For example, the incubation temperature is 1-5°C, such as 1°C, 2°C, 3°C, 4°C, 5°C. For example, the incubation time is 8-18h, such as 8-14h, 10-12h.
[0344] According to an embodiment of the present invention, the sealing treatment comprises: sealing the coated well plate obtained in step (S2) with a skimmed milk powder solution. For example, the skimmed milk powder can be skimmed milk powder. For example, the mass fraction of the skimmed milk powder solution is 5%.
[0345] According to an embodiment of the present invention, the sealing treatment time is 0.5 to 2 hours, and the temperature is 30 to 45° C. According to a specific embodiment of the present invention, the sealing treatment time is 1 hour, and the temperature is 37° C.
[0346] According to an embodiment of the present invention, in step (S3), the contact time is 0.5 to 2 hours, and the temperature is 30 to 45° C. Exemplarily, the contact time is 1 hour, and the temperature is 37° C.
[0347] Beneficial effects of the present invention:
[0348] 1. The present invention uses polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) to encapsulate quantum dots, thereby achieving the stable existence of quantum dot materials in the aqueous phase and almost completely retaining the optical properties of the quantum dots;
[0349] 2. The product of the present invention can obtain fluorescent groups with different emission wavelength ranges by adjusting the quantum dot components;
[0350] 3. The present invention uses degradable polylactic acid to coat quantum dot materials to construct biological nanoprobes, which not only retains the high fluorescence intensity and narrow emission of quantum dots, but also gives them good biocompatibility, non-toxicity, and environmental protection characteristics;
[0351] 4. Since perovskite quantum dots have the characteristic of narrow emission peak (<20nm), the hydrophobic quantum dot nanocrystals of the present invention can be used as bio-nanoprobes in the medical field for simultaneous detection of multiple analytes, and can avoid false negative results caused by crossover of emission peaks of fluorescent substances, thereby improving the reliability of detection, having universality, greatly meeting the needs of modern biotechnology and medical detection, and having important significance in the field of medical diagnosis and treatment;
[0352] 5. The novel biological nanoprobe provided by the present invention, which is constructed based on stable quantum dot materials in the aqueous phase, realizes biological detection with high sensitivity and high fluorescence intensity.
[0353] A hydrophobic quantum dot nano material comprises quantum dots and carboxyl-terminated polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) coated on the surface of the quantum dots.
[0354] The hydrophobic quantum dot nanomaterial, wherein the quantum dots are selected from modified or unmodified quantum dots as shown below: perovskite quantum dots, carbon quantum dots, cadmium quantum dots or sulfur quantum dots;
[0355] Preferably, the hydrophobic quantum dot nanomaterial is prepared by coating the surface of quantum dots with carboxyl-terminated poly(lactic acid-glycolic acid) copolymer (OH-PLGA-COOH).
[0356] Preferably, the number average molecular weight of the carboxyl-terminated polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) is 100 to 100,000;
[0357] Preferably, the hydrophobic quantum dot nanomaterial is a nanocrystal;
[0358] Preferably, the coating is complete coating;
[0359] Preferably, the average particle size of the quantum dots is 5 to 20 nm; the average particle size of the hydrophobic quantum dot nanomaterial is larger than the average particle size of the quantum dots;
[0360] Preferably, the modification refers to modifying the quantum dots with a fluorescent group (eg, sulfydryl).
[0361] The preparation method of the hydrophobic quantum dot nanomaterial comprises the following steps: coating the surface of the quantum dots with carboxyl-terminated polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) to obtain the hydrophobic quantum dot nanomaterial.
[0362] The method for preparing the hydrophobic quantum dot nanomaterial comprises the following specific steps:
[0363] (A1) mixing the raw materials for preparing quantum dots and the carboxyl-terminated poly(lactic acid-glycolic acid) copolymer in a solvent, and after the mixture is completely dissolved, adding a ligand material to form a stable solution;
[0364] (A2) adding the above-mentioned stable solution to an anti-solvent to form a hydrophobic quantum dot nanomaterial solution, and then precipitating the hydrophobic quantum dot nanomaterial using an anti-solvent supersaturation method;
[0365] Preferably, in step (A1), the molar mass ratio of the quantum dots to the carboxyl-terminated poly(lactic acid-glycolic acid) copolymer (OH-PLGA-COOH) is 1 mmol: (300-600) mg;
[0366] Preferably, in step (A1), the mass volume ratio of the carboxyl-terminated polylactic acid-glycolic acid copolymer to the solvent is (5-30) mg:1 mL;
[0367] Preferably, in step (A1), the solvent can be selected from one or both of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO);
[0368] Preferably, in step (A1), the ligand material may be selected from oleic acid, oleylamine and / or sulfydryl;
[0369] Preferably, the volume ratio of the added amount of the ligand material to the solvent is (0.5-5):10;
[0370] Preferably, step (A1) is carried out under anhydrous and oxygen-free conditions;
[0371] Preferably, in step (A2), the anti-solvent is selected from at least one of toluene, chlorobenzene and n-hexane;
[0372] Preferably, the volume ratio of the stabilizing solution to the antisolvent is (0.1-5):10;
[0373] Preferably, the volume ratio of the hydrophobic quantum dot nanomaterial solution to the antisolvent is (0.5-3):15;
[0374] Preferably, the method for preparing the hydrophobic quantum dot nanomaterial further comprises step (A3), separating the precipitated hydrophobic quantum dot nanomaterial from the solution system, and drying to obtain a solid hydrophobic quantum dot nanomaterial;
[0375] Preferably, the method for preparing the hydrophobic quantum dot nanomaterial further comprises a step (A4), dispersing the solid hydrophobic quantum dot nanomaterial obtained in step (A3) in water to obtain an aqueous dispersion of the hydrophobic quantum dot nanomaterial.
[0376] A nanoprobe, comprising the hydrophobic quantum dot nanomaterial according to claim 1 or 2;
[0377] Preferably, the nanoprobe is a biological material labeled with the hydrophobic quantum dot nanomaterial, and is formed by coupling the hydrophobic quantum dot nanomaterial with the biological material;
[0378] Preferably, the biomaterial may be selected from one, two or more of antibodies, aptamers, polypeptides, etc.;
[0379] Preferably, the mass ratio of the hydrophobic quantum dot nanomaterial to the biomaterial is (10-50):1, preferably 20:1;
[0380] Preferably, the average particle size of the nanoprobes is between 100 and 500 nm.
[0381] The preparation method of the nanoprobe comprises coupling the hydrophobic quantum dot nanomaterial and the biomaterial to form the nanoprobe;
[0382] Preferably, the preparation method specifically comprises the following steps: dispersing the hydrophobic quantum dot nanomaterial in a cross-linking reagent solution, adding biomaterial and surfactant thereto, and obtaining the nanoprobe.
[0383] The method for preparing the nanoprobe comprises the following steps:
[0384] (B1) dispersing a hydrophobic quantum dot nanomaterial in a cross-linking reagent solution and stirring to activate the carboxyl groups on the surface of the hydrophobic quantum dot nanomaterial;
[0385] (B2) adding a biological material and a surfactant to the solution obtained in step (B1) to obtain the nanoprobe;
[0386] Preferably, the cross-linking reagent is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS); preferably, the mass ratio of EDC to NHS is 1:(3-10);
[0387] Preferably, the solvent in the cross-linking reagent solution is PBS buffer;
[0388] Preferably, the cross-linking reagent solution is a mixture of EDC and NHS;
[0389] Preferably, the mass ratio of the biomaterial to the cross-linking agent is (5-15):1;
[0390] Preferably, the surfactant is a nonionic surfactant;
[0391] Preferably, the nonionic surfactant is one, two or three of Triton X-100, alkyl polyglycoside APG and fatty alcohol polyoxyethylene ether AEO.
[0392] Preferably, in step (B2), when the biomaterial and the surfactant are added to the solution obtained in step (B1), a gentle reaction is carried out on a shaking table;
[0393] Preferably, step (B2) further comprises refrigerating the nanoprobes.
[0394] A kit comprises the hydrophobic quantum dot nanomaterial or the nanoprobe.
[0395] Application of the hydrophobic quantum dot nanomaterial, the nanoprobe or the kit in the field of medical detection and medical diagnosis and treatment;
[0396] Preferably, the medical detection is cell imaging or biological detection;
[0397] Preferably, the nanoprobe or kit can specifically recognize the following target analytes: antibodies, aptamers, polypeptides, antigens, target molecules or proteases.
[0398] A method for specifically identifying a target analyte, the method comprising: contacting the nanoprobe with the target analyte, and identifying the target analyte through fluorescence detection; the target analyte has the aforementioned selection. BRIEF DESCRIPTION OF THE DRAWINGS
[0399] Figure 1 3 is a transmission electron microscope image of the water-soluble perovskite nanocrystal of Example 1. As can be seen from the image, the particle size of the water-soluble perovskite nanocrystal is about 100 nm.
[0400] Figure 2 PL spectra of perovskite quantum dots dissolved in toluene (PQDs-Toluene) and water-soluble perovskite nanocrystals (PNCs-water).
[0401] Figure 3This is the Confocal image of fluorescence imaging of perovskite-based nanoprobes on brain glioma cells. The Confocal laser excitation wavelengths are 405nm and 488nm. Figure 4 This is a Confocal image of fluorescence imaging of perovskite-based nanoprobes on brain glioma tissue slices. The Confocal laser excitation wavelengths are 405nm and 488nm.
[0402] Figure 5 Actual picture of perovskite-based nanoprobes imaging in living brain glioma tissue.
[0403] Figure 6 This is a transmission electron microscopy image of the PQDs quantum dots prepared in Preparation Example 11, and the image shows that the size of the PQDs quantum dots is ∼12 nm.
[0404] Figure 7 This is a transmission electron microscope image of the P-PQDs nanocrystals of Preparation Example 11, and the image shows that the size of the P-PQDs quantum dots is ~30nm.
[0405] Figure 8 This is the fluorescence imaging image of the P-PQDs perovskite nanocrystals of Example 11 under excitation at 420-450nm, which is green.
[0406] Fig. 9 Fluorescence emission spectra of P-PQDs nanocrystals and Probe-P QDs of Preparation Example 11.
[0407] Fig.10 Zeta potential diagram of P-PQDs quantum dots, CTX and Probe-P QDs in Example 21.
[0408] Fig.11 This is the Confocal fluorescence imaging of the biological nanoprobe Probe-PQDs formed by the P-PQDs perovskite nanocrystals and CTX in Example 31, which specifically recognizes brain glioma 251 cells and the control group almost does not recognize HA cells, with dual-channel 405nm and 488nm excitation.
[0409] Fig.12 CsPbBr prepared in Example 12 3 -Fluorescence emission spectrum and absorption spectrum of QDs quantum dots.
[0410] Fig.13 CsPbBr prepared in Example 12 3 -Transmission electron microscope image of QDs quantum dots (left) and their lattice fringes (right).
[0411] Fig.14 CsPbBr prepared in Example 22 3-Transmission electron microscopy image of QDs@PLGA perovskite nanocrystals, the particle size of the nanocrystals is ~80nm.
[0412] Fig.15 CsPbBr prepared in Example 22 3 -Surface morphology of QDs@PLGA perovskite nanocrystals, the particle size of the nanocrystals is ~80nm.
[0413] Fig.16 CsPbBr 3 -QDs quantum dots and CsPbBr 3 -XRD pattern of QDs@PLGA perovskite nanocrystals.
[0414] Fig.17 CsPbBr 3 -QDs quantum dots and CsPbBr 3 -QDs@PLGA perovskite nanocrystals.
[0415] Fig.18 CsPbBr prepared in Example 32 3 -Zeta potential diagrams of QDs@PLGA, human IgG, and probe CsPbBr3-QDs@PLGA@IgG in MES buffer solution (pH=5.15), PBS buffer solution (pH=7.3), Tris buffer solution (pH=8.17), etc.
[0416] Fig.19 The transmission electron microscope image of the PQDs quantum dots and their lattice fringes of Preparation Example 13; the left image represents the transmission electron microscope image of the quantum dots, and the particle size of the quantum dots is ~12nm; the right image represents the fringes spacing of 0.295nm.
[0417] Fig. 20 The fluorescence emission spectrum and absorption spectrum of the PQDs quantum dots prepared in Example 13 show that the emission peak of the quantum dots is 515 nm.
[0418] Fig.21 The fluorescence emission spectrum and absorption spectrum of the Sulfydryl-PQDs quantum dots of Preparation Example 23, the emission peak of the quantum dots is 461nm.
[0419] Fig. 22 This is a transmission electron microscopy image of the PQDs@PLGA perovskite nanocrystals of Example 13.
[0420] Fig.23 This is an optical microscope image of the PQDs@PLGA perovskite nanocrystal of Example 13. The left image represents the fluorescence imaging of the nanocrystal under excitation at 420-450nm, and the right image represents the bright field image of the nanocrystal.
[0421] Fig.24 2. The fluorescence emission spectrum and absorption spectrum of the PQDs@PLGA perovskite nanocrystals of Example 13.
[0422] Fig.25 The SEM image and EDS spectrum of the biological nanoprobe PQDs@PLGA@IgG formed by coupling the PQDs@PLGA perovskite nanocrystals of Example 23 with human IgG antibodies.
[0423] Fig.26 This is the Confocal fluorescence imaging of the PQDs@PLGA perovskite nanocrystals of Example 33 coupled with human IgG antibodies to form the bio-nanoprobe PQDs@PLGA@IgG, and verified by recognition with Eu-labeled anti-human IgG, with dual-channel 488nm and 561nm excitation.
[0424] Fig. 27 Schematic diagram of the experiment in which the PQDs@PLGA perovskite nanocrystals of Example 33 are coupled with human IgG antibodies to form the bio-nanoprobe PQDs@PLGA@IgG, and then identified and verified with Eu-labeled anti-human IgG. DETAILED DESCRIPTION
[0425] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0426] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0427] Example 1
[0428] The steps for preparing water-soluble perovskite nanocrystals are as follows:
[0429] (1) In a room temperature and air environment, 42.5 mg CsBr and 73.4 mg PbBr 2 25 mg of terminally modified thiol distearoylphosphatidylcholine polyethylene glycol (DSPC-PEG-COOH, Mw=3400) was dissolved in 5 mL of N,N-dimethylformamide (DMF) solvent. After complete dissolution, 0.5 mL of oleic acid and 0.25 mL of oleylamine were added to form a stable precursor solution.
[0430] (2) 500 μL of the above solution was slowly added dropwise into 10 mL of a vigorously stirred toluene solution to obtain a perovskite quantum dot solution; the reaction was stirred for 4 h to allow complete coating to obtain water-soluble perovskite nanocrystals.
[0431] (3) Separation and purification of water-soluble perovskite nanocrystals: The toluene solution in the above (2) was centrifuged at 10,000 r for 20 min, and the obtained precipitate was air-dried in a fume hood to obtain a light yellow powder, which turned green under ultraviolet light.
[0432] (4) The powder was dispersed in water by ultrasonication for 5 min, and the water-soluble perovskite nanocrystal solution was stored at room temperature.
[0433] Figure 1 3 is a transmission electron microscope image of the water-soluble perovskite nanocrystal of Example 1. As can be seen from the image, the particle size of the water-soluble perovskite nanocrystal is about 200 nm.
[0434] Figure 2 PL spectra of perovskite quantum dots dissolved in toluene (PQDs-Toluene) and water-soluble perovskite nanocrystals (PNCs-water); Figure 2 It can be seen from the PL spectrum that water-soluble perovskite nanocrystals can exist stably in the aqueous phase, almost retain the optical properties of perovskite quantum dots, and the coated particle size is uniform.
[0435] Example 2
[0436] A method for preparing a perovskite nanocrystal probe for rapid detection of brain glioma tissue imaging, the specific steps are as follows:
[0437] (1) D-PNCs (e.g., wavelength of 520 nm) are dissolved in ultrapure water and ultrasonicated for 5 min to make them uniformly dispersed in the solvent.
[0438] (2) adding an antibody (e.g., the antibody is chlorotoxin CTX), shaking at 37°C, and reacting for 10 min;
[0439] (3) After the reaction is completed, the solution is concentrated to 30-100 ul using an ultrafiltration centrifuge tube with a molecular cutoff of 30-100 KDa. The concentrate is then purified using a gel size exclusion method. The fluorescent portion is collected and concentrated using an ultrafiltration centrifuge tube. The portion is then stored in a diluent (containing 0.05% Triton X-100) and stored at 4°C for later use. The probe solution is obtained.
[0440] Example 3
[0441] The specific steps of the present invention for simple and rapid diagnosis of brain glioma and the evaluation criteria for canceration of brain glioma
[0442] Scope of use: The target detection substances can be brain glioma cells, frozen sections during brain glioma sectioning surgery, paraffin sections, and living tissues removed during brain glioma surgery.
[0443] Usage: Take 200-300ul of the test solution and drop it onto the slice to be tested. Let it react at room temperature for 10 minutes. After the reaction, rinse it with a rinse solution (such as ultrapure water) for 5-6 times, and observe the image with a handheld UV lamp.
[0444] Evaluation criteria for glioma canceration: Use an ordinary handheld ultraviolet lamp with a wavelength of 320 to 450 nm to irradiate the target object to be detected. According to the principle of antibody-antigen specific recognition, when the target object to be detected contains relevant antigens of the glioma area, the detection solution is added to the target object to be detected, react for 10 minutes, and then use the flushing solution to rinse the detection solution 5-6 times. When the tumor area is excited and irradiated by the handheld ultraviolet lamp, fluorescence appears, and the test result is the glioma tumor area; conversely, when the target object to be detected is normal tissue, that is, it does not contain relevant antigens of the glioma area, there is no fluorescence in the tumor area under the excitation and irradiation of the handheld ultraviolet lamp, and the test result is the normal tissue area, that is, the non-tumor area; the higher the fluorescence intensity, the higher the degree of glioma canceration in the target object to be detected, and conversely, the lower the fluorescence intensity, the lower the degree of canceration.
[0445] Figure 3 This is a Confocal image of fluorescence imaging of perovskite-based nanoprobes on glioma cells. The Confocal laser excitation wavelengths are 405nm and 488nm. 172 glioma cells were selected as the experimental group, and it can be seen that they show green fluorescence; HA cells are normal glial cells, which show no fluorescence; the targeting functionality of perovskite nanocrystal probes has been successfully verified.
[0446] Figure 4 This is a Confocal image of fluorescence imaging of perovskite-based nanoprobes on brain glioma tissue slices. The Confocal laser excitation wavelengths are 405nm and 488nm.
[0447] Figure 4 The above picture is the negative control group. The detection liquid consists only of perovskite quantum dots. From the results in the picture, it can be seen that there is no fluorescence, indicating no specific recognition.
[0448] Figure 4 The figure below is the experimental group. The components of this detection solution are water-soluble perovskite nanocrystals or water-soluble perovskite quantum dot probes. From the results in the figure, we can see that there is a strong green fluorescence, indicating that due to the presence of specific recognition antibodies, specific recognition of antibodies and antigens occurs, verifying the specific recognition function of the detection solution.
[0449] Figure 5 This is a real picture of perovskite-based nanoprobes imaging in living glioma tissue. Handheld UV lamp imaging 10W, 365nm. The picture shows the staining of living tissue of mice with glioma. When illuminated by a handheld UV lamp, it shows green fluorescence, verifying the targeting functionality of the nanoprobe on the living tissue.
[0450] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0451] The carboxyl-terminated poly(lactic acid-glycolic acid) copolymer (OH-PLGA-COOH) used in the following examples was purchased from Jinan Daigang Bioengineering Co., Ltd., with a number average molecular weight of 110,000 and a ratio of DLLA:GA of 50:50.
[0452] Preparation Example 11
[0453] The preparation steps of PQDs perovskite quantum dots are as follows:
[0454] (1) 42.5 mg CsBr and 73.4 mg PbBr 2 Dissolve in 5 mL of N,N-dimethylformamide (DMF) solvent. After complete dissolution, add 0.5 mL of oleic acid and 0.25 mL of oleylamine to stabilize the solution.
[0455] (2) Take 500 μL of the above solution and place it in a glove box. 2 Under atmosphere protection, slowly add it dropwise into 10 mL of vigorously stirred toluene solution to obtain a PQDs quantum dot solution.
[0456] (3) The prepared PQDs perovskite quantum dots were centrifuged at 10000 r / min for 20 min to separate the supernatant, that is, the purified PQDs perovskite quantum dots solution was obtained, and the solution was bright green.
[0457] Figure 6 This is the transmission electron microscope image of the prepared PQDs perovskite quantum dots. From the image, we can see that the particle size of the quantum dots is ~12nm, which is consistent with the CsPbBr 3 Quantum dot size.
[0458] Embodiment 11
[0459] P-PQDs water-soluble perovskite nanocrystals
[0460] In order to achieve the hydrophobic effect, based on Preparation Example 11, the hydrophobic carboxyl-terminated polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) is coated on the surface of the highly fluorescent perovskite quantum dots to form water-soluble perovskite nanocrystals, and the steps are as follows:
[0461] (1) 42.5 mg CsBr and 73.4 mg PbBr 2 90 mg of carboxyl-terminated poly(lactic acid-co-glycolic acid) (OH-PLGA-COOH) was dissolved in 5 mL of N,N-dimethylformamide (DMF) solvent. After complete dissolution, 0.5 mL of oleic acid and 0.25 mL of oleylamine were added to stabilize the solution.
[0462] (2) 750 μL of the above solution was slowly added dropwise into 15 mL of vigorously stirred toluene solution to obtain a P-PQDs perovskite nanocrystal solution; the reaction was stirred for 8 h to ensure complete coating and obtain water-soluble P-PQDs perovskite nanocrystals.
[0463] (3) Separate and purify P-PQDs perovskite nanocrystals by centrifuging them at 10,000 r / min for 20 min. Dry the obtained precipitate in an oven at 60°C for 1 h to obtain a dark yellow powder, which turns green under 365 nm ultraviolet light.
[0464] (4) The powder is dispersed in water and the water-soluble P-PQDs perovskite nanocrystals are stored at room temperature.
[0465] Figure 7 is a transmission electron microscope image of the water-soluble P-PQDs perovskite nanocrystal prepared in Example 11. Fig.21 It can be seen that the average particle size of P-PQDs perovskite nanocrystals is 50 nm, which is larger than that of Preparation Example 11, indicating that the carboxyl-terminated polylactic acid-hydroxyacetic acid copolymer coats multiple PQDs quantum dots into an overall morphology, and the coating effect is good.
[0466] Figure 8 This is a fluorescence imaging image of the P-PQDs perovskite nanocrystals of Example 11 under excitation at 420-450nm.
[0467] Embodiment 21
[0468] Water-soluble perovskite nanocrystal bio-nanoprobes
[0469] In order to further couple the hydrophobic perovskite nanocrystals with biomaterials to construct a new type of nanobiological probe, based on Example 1, the high positive charge performance of the perovskite quantum dot surface can be utilized to connect with the negatively charged biomaterial through the electrostatic interaction of positive and negative charges to construct a water-soluble perovskite nanocrystal probe. The specific implementation steps are as follows:
[0470] (1) The chlorotoxin polypeptide was dissolved in ultrapure water (pH=6.42) and the concentration of the solution was adjusted to 10 mg / mL.
[0471] (2) Take 1 mL of 0.1 mg / mL P-PQDs solution and mix it with 10 ul of 10 mg / mL chlorotoxin peptide, vortex for 30 seconds to mix them evenly, and store the prepared Probe-PQDs probe solution at 4°C.
[0472] Fig. 9 : is the fluorescence emission spectra of P-PQDs and nanoprobe Probe-PQDs in Example 21. Fig. 9 It can be seen that a slight blue shift will occur when P-PQDs are connected to biomaterials. This is because the size of P-PQDs changes due to the connection to biomaterials, resulting in a slight change in the corresponding spectrum. It can also be seen that the nanoprobe Probe-PQDs almost completely retains the optical properties of the original P-PQDs.
[0473] Embodiment 31
[0474] Nanoprobes identify brain glioma 251 cells
[0475] After the construction of the biological nanoprobe is completed, the recognition function of the probe is verified. On the basis of Example 2, the conventional experimental method in biological experiments is used to verify the recognition function of the probe. In this example, the nanoprobe P-PQDs prepared in Example 21 is used to label the chlorotoxin polypeptide, and the target analytes are brain glioma U251 cells and HA cells.
[0476] (1) U251 cells and HA cells were cultured at 1×10 5 The cells were seeded in confocal dishes at a density of 100 cells / mL and incubated at 37°C in CO. 2 Culture in an incubator.
[0477] (2) Take out the confocal dish and rinse the cells three times with PBS (0.01 M, PH=7.3).
[0478] (3) Add 2 mL of 4% paraformaldehyde and fix for 15 min, then rinse the cells three times with PBS (0.01 M, PH=7.3).
[0479] (4) Add 2 mL of goat serum working solution for blocking for 30 min, and then rinse the cells three times with PBS (0.01 M, PH = 7.3).
[0480] (5) Add 1 mL of the prepared 0.1 mg / mL Probe-PQDs probe and identify at room temperature for 1 h.
[0481] (6) Recover the probe solution and rinse the cells again with PBS (0.01 M, pH = 7.3) 4 to 6 times.
[0482] (7) Counterstain the cell nucleus with DAPI (1 mg / ml), incubate in the dark for 15 min, and rinse the cells 4 to 6 times with PBS (0.01 M, PH = 7.3).
[0483] (8) Observe with confocal microscope. Dual channel excitation at 405nm and 488nm.
[0484] Fig.11This is the Confocal fluorescence imaging diagram of the Probe-PQDs probe in Example 31 for the recognition verification of U251 cells and HA cells, with dual-channel 405nm and 488nm excitation. The 405nm channel corresponds to the DAPI channel; the 488nm channel corresponds to the Probe-PQDs. It can be intuitively seen from the figure that the Probe-PQDs specifically recognizes the brain glioma U251 cells, but almost does not recognize the HA cells that hardly express it, which is consistent with the theoretical basis.
[0485] The biomaterial in the above embodiment can also be replaced by an aptamer or an antibody to obtain a nanoprobe in which the perovskite nanocrystal is coupled with the aptamer or the antibody. The obtained nanoprobe also has a specific recognition function.
[0486] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0487] Example 12
[0488] A CsPbBr 3 -QDs perovskite quantum dots synthesis method, the steps are as follows:
[0489] (1) 0.2 mmol CsBr and 0.2 mmol PbBr 2 Dissolve in 5 mL of N,N-dimethylformamide (DMF) solvent. After complete dissolution, add 0.5 mL of oleic acid and 0.25 mL of oleylamine to stabilize the solution.
[0490] (2) Take 0.5 mL of the above solution and slowly add it dropwise into 10 mL of vigorously stirred toluene solution to obtain CsPbBr 3 -QDs quantum dot solution.
[0491] (3) The prepared CsPbBr 3 -QDs perovskite quantum dots were centrifuged at 10000r for 10 min, and the supernatant was separated to obtain the purified CsPbBr 3 -QDs perovskite quantum dots solution.
[0492] Fig.12 CsPbBr prepared in Example 12 3 -QDs perovskite quantum dots fluorescence emission spectrum and absorption spectrum. It can be seen from the figure that the CsPbBr prepared in this embodiment 3 -QDs perovskite quantum dots have a maximum emission peak of 514nm, and CsPbBr 3 -QDs perovskite quantum dots have a half-peak width of 18nm. This shows that the CsPbBr prepared in this example 3-QDs perovskite quantum dots have a narrow fluorescence emission half-width, and their absorption edge corresponds to the maximum emission peak of 514nm.
[0493] Fig.13 CsPbBr prepared in Example 12 3 -QDs perovskite quantum dots transmission electron microscope image (left) and its lattice fringe image (right). Fig.13 It can be seen from the transmission electron microscope image (left) that the CsPbBr prepared in this embodiment 3 -QDs perovskite quantum dots have a particle size of about 12nm. Fig.13 The lattice fringe diagram (right figure) shows that the CsPbBr prepared in this embodiment 3 -QDs perovskite quantum dots have a stripe spacing of 0.295nm. This shows that the CsPbBr prepared in this example 3 -QDs perovskite quantum dots have good quality and uniform particle size.
[0494] Embodiment 22
[0495] To further achieve the hydrophobic effect, based on Example 12, a hydrophobic polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) containing terminal carboxyl groups is coated on the surface of the highly fluorescent perovskite quantum dots to form hydrophobic perovskite nanocrystals, and the steps are as follows:
[0496] (1) 0.2 mmol CsBr and 0.2 mmol PbBr 2 and 90 mg of poly(lactic acid-co-glycolic acid) (OH-PLGA-COOH) containing terminal carboxyl groups were dissolved in 5 mL of N,N-dimethylformamide (DMF) solvent. After complete dissolution, 0.5 mL of oleic acid and 0.25 mL of oleylamine were added to stabilize the solution;
[0497] (2) Take 0.5 mL of the mixed solution prepared in step (1) and add it dropwise to 10 mL of vigorously stirred toluene solution to obtain CsPbBr 3 -QDs@PLGA quantum dot solution;
[0498] (3) Take 1 mL of the solution obtained in step (2) and add it to 15 mL of toluene solution. Stir and react for 48 h to complete the coating to obtain CsPbBr 3 -QDs@PLGA perovskite nanocrystal mixed solution;
[0499] (4) CsPbBr prepared in step (3) 3 -QDs@PLGA perovskite nanocrystal mixed solution was centrifuged at 10000 r for 10 min, and the obtained precipitate was dried in an oven at 60 °C for 1 h;
[0500] (5) Add 2-4 mL of water to the dried product of step (4) and perform ultrasonic treatment for 2 min to obtain a uniformly dispersed CsPbBr 3 -QDs@PLGA perovskite nanocrystal dispersion. Fig.14 CsPbBr prepared in Example 22 3 -QDs@PLGA perovskite nanocrystals. It can be seen from the figure that the CsPbBr prepared in this embodiment 3 -QDs@PLGA perovskite nanocrystals have a particle size of about 80 nm, which is smaller than that of CsPbBr prepared in Example 12. 3 -QDs perovskite quantum dots have increased in size, indicating that carboxyl-terminated poly(lactic acid-co-glycolic acid) (OH-PLGA-COOH) has been successfully coated on CsPbBr 3 -QDs perovskite quantum dots. Therefore, it is expected to be used in many fields such as biological detection.
[0501] Fig.15 CsPbBr prepared in Example 22 3 -QDs@PLGA perovskite nanocrystals. As can be seen from the figure, the CsPbBr 3 -QDs@PLGA perovskite nanocrystals have a particle size of about 80 nm, and CsPbBr 3 -QDs@PLGA perovskite nanocrystal particles are evenly dispersed and consistent with its transmission electron microscopy characterization results.
[0502] Fig.16 CsPbBr prepared in Example 12 3 -QDs perovskite nanocrystals (below) and CsPbBr prepared in Example 22 3 -QDs@PLGA perovskite nanocrystal (top) XRD pattern. From the results in the figure, it can be seen that the CsPbBr prepared in Example 12 of the present invention 3 -QDs perovskite quantum dots have strong and sharp diffraction peaks, are pure phase structures, and have good quality. The CsPbBr formed by coating with carboxyl-terminated polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) 3 The diffraction peak intensity of -QDs@PLGA perovskite nanocrystals is slightly reduced, which further indicates that the carboxyl-terminated poly(lactic acid-co-glycolic acid) (OH-PLGA-COOH) polymer coating of the present invention is successful.
[0503] Fig.17 CsPbBr prepared in Example 12 3 -QDs perovskite nanocrystals and CsPbBr prepared in Example 22 3-QDs@PLGA perovskite nanocrystal quantum yield bar graph. It can be concluded from the figure that the CsPbBr prepared by the present invention 3 The quantum yield of perovskite quantum dots is as high as 83.10%, indicating that they have high fluorescence intensity. 3 The quantum yield of -QDs@PLGA perovskite nanocrystals is still as high as 70.07%, indicating that carboxyl-terminated poly(lactic-co-glycolic acid) (OH-PLGA-COOH) is coated on CsPbBr 3 -QDs perovskite nanocrystals not only achieve the stable existence of perovskite quantum dots in the aqueous phase, but also almost completely retain the optical properties of perovskite quantum dots (with little effect on their fluorescence intensity). The hydrophobic CsPbBr formed after coating with carboxyl-terminated poly(lactic acid-glycolic acid copolymer) (OH-PLGA-COOH) 3 -QDs@PLGA perovskite nanocrystals still have high fluorescence intensity.
[0504] Embodiment 32
[0505] Hydrophobic perovskite nanocrystals for aqueous fluorescence detection applications:
[0506] The hydrophobic CsPbBr3-QDs@PLGA perovskite nanocrystals formed after coating with carboxyl-terminated poly(lactic acid-glycolic acid) copolymer (OH-PLGA-COOH) have negative charges in solution due to the large number of -COOH functional groups exposed on the surface. The essence of an antibody is a protein, which is also an amphoteric electrolyte. When the pH of the external solution is greater than the isoelectric point pI value of the zwitterion, the zwitterion releases protons and carries a negative charge; when the pH of the external solution is less than the pI value of the zwitterion, the zwitterion is protonated and carries a positive charge. Therefore, the charge of the antibody can be regulated by adjusting the pH value of the buffer solution. Through charge electrostatic interactions, we can make the hydrophobic CsPbBr 3 -QDs@PLGA perovskite nanocrystals are coupled with antibodies (e.g., IgG, IgM, IgA, etc.) to form a new type of perovskite nanocrystal biological probe. The specific steps are as follows:
[0507] (1) Prepare several common buffer solutions in biology: MES buffer solution (pH = 5.15), PBS buffer solution (pH = 7.3), and Tris buffer solution (pH = 8.17).
[0508] (2) 200 mg of CsPbBr prepared in Example 22 was added 3-QDs@PLGA perovskite nanocrystals were added to 2 mL of MES buffer solution (pH = 5.15), PBS buffer solution (pH = 7.3), and Tris buffer solution (pH = 8.17), respectively, at room temperature and magnetic stirring at 300 r for 30 min;
[0509] (3) 10 μL of human IgG antibody (1 mg / mL) and 4 μL of Triton X-100 were added to the buffer solution of step (2) and reacted in a shaker at 37°C for 30 min to obtain CsPbBr 3 -QDs@PLGA perovskite nanocrystal labeled human IgG probe CsPbBr 3 -QDs@PLGA@IgG;
[0510] (4) The probe CsPbBr prepared in step (3) 3 -QDs@PLGA@IgG was stored in a refrigerator at 4°C.
[0511] Fig.18 CsPbBr prepared in Example 32 3 Zeta potential diagrams of -QDs@PLGA, human IgG, and probe CsPbBr3-QDs@PLGA@IgG in MES buffer solution (pH=5.15), PBS buffer solution (pH=7.3), Tris buffer solution (pH=8.17), etc. It can be seen from the figure that CsPbBr 3 -QDs@PLGA has negative charges in acidic, neutral, and alkaline solutions such as pH=5.15, pH=7.3, and pH=8.17; human IgG antibodies have positive charges under acidic conditions of pH=5.15, and negative charges in neutral and alkaline solutions such as pH=7.3 and pH=8.17; therefore, placing CsPbBr3-QDs@PLGA perovskite nanocrystals and human IgG in MES (pH=5.15) buffer solution can achieve charge electrostatic interaction to construct CsPbBr 3 -QDs@PLGA novel perovskite nanocrystal probe.
[0512] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0513] The carboxyl-terminated poly(lactic acid-glycolic acid) copolymer (OH-PLGA-COOH) used in the following examples was purchased from Jinan Daigang Bioengineering Co., Ltd., with a number average molecular weight of 30,000 and a DLLA:GA ratio of 75:25.
[0514] Preparation Example 13
[0515] The preparation steps of PQDs perovskite quantum dots are as follows:
[0516] (1) 42.5 mg CsBr and 73.4 mg PbBr 2 Dissolve in 5 mL of N,N-dimethylformamide (DMF) solvent. After complete dissolution, add 0.5 mL of oleic acid and 0.25 mL of oleylamine to stabilize the solution.
[0517] (2) Take 500 μL of the above solution and place it in a glove box. 2 Under atmosphere protection, slowly add it dropwise into 10 mL of vigorously stirred toluene solution to obtain a PQDs quantum dot solution.
[0518] (3) The prepared PQDs perovskite quantum dots were centrifuged at 10000 r / min for 20 min to separate the supernatant, that is, the purified PQDs perovskite quantum dots solution was obtained, and the solution was bright green.
[0519] Fig.19 The transmission electron microscopy image of the prepared PQDs perovskite quantum dots and their lattice fringes. The left image represents the transmission electron microscopy image. The particle size of the quantum dots is ~12nm, which is consistent with the CsPbBr 3 Quantum dot size; the right picture shows that the fringe spacing is 0.295nm, which means that the quantum dots synthesized by this method have good quality and uniform particle size.
[0520] Fig. 20 The fluorescence emission spectrum and absorption spectrum of the prepared PQDs perovskite quantum. Fig. 20 It can be seen that PQDs perovskite quantum dots can produce strong fluorescence under 365nm excitation, with an emission peak of 515nm and a half-peak width of 18nm, indicating that the fluorescence emission of the quantum dots is narrow and the absorption edge corresponds to an emission peak of 515nm.
[0521] Preparation Example 23 Preparation of Sulfydryl-PQDs Perovskite Quantum Dots
[0522] (1) 42.5 mg CsBr and 73.4 mg PbBr 2 Dissolve in 5 mL of N,N-dimethylformamide (DMF) solvent. After complete dissolution, add 0.5 mL of oleic acid, 0.25 mL of oleylamine, and 0.2 mL of sulfydryl to stabilize the solution.
[0523] (2) Take 500 μL of the above solution and place it in a glove box. 2 Under atmosphere protection, slowly add it dropwise into 10 mL of vigorously stirred toluene solution to obtain a PQDs quantum dot solution.
[0524] (3) The prepared Sulfydryl-PQDs perovskite quantum dots were centrifuged at 10,000 r / min for 20 min to separate the supernatant, i.e., the purified PQDs perovskite quantum dot solution was obtained. The solution was transparent cyan; under ultraviolet light (365 nm), the solution appeared blue.
[0525] Fig.21 The fluorescence emission spectrum and absorption spectrum of the prepared Sulfydryl-PQDs perovskite quantum dot. Fig.21 It can be seen that Sulfydryl-PQDs perovskite quantum dots can produce strong fluorescence under 365nm excitation, and its emission peak is 461nm. Therefore, by adjusting the perovskite quantum dot components, fluorescent groups with different emission wavelength ranges can be obtained.
[0526] Example 13 PQDs@PLGA hydrophobic perovskite nanocrystals
[0527] In order to achieve the hydrophobic effect, based on Preparation Example 13, the hydrophobic carboxyl-terminated polylactic acid-glycolic acid copolymer (OH-PLGA-COOH) is coated on the surface of the highly fluorescent perovskite quantum dots to form hydrophobic perovskite nanocrystals, and the steps are as follows:
[0528] (1) 42.5 mg CsBr and 73.4 mg PbBr 2 90 mg of carboxyl-terminated poly(lactic acid-co-glycolic acid) (OH-PLGA-COOH) was dissolved in 5 mL of N,N-dimethylformamide (DMF) solvent. After complete dissolution, 0.5 mL of oleic acid and 0.25 mL of oleylamine were added to stabilize the solution.
[0529] (2) Take 500 μL of the above solution and slowly add it dropwise into 10 mL of vigorously stirred toluene solution to obtain PQDs@PLGA quantum dot solution; then take 1 mL of the obtained solution and add it into 15 mL of toluene solution, stirring and reacting for 48 hours to ensure complete coating, thereby obtaining hydrophobic PQDs@PLGA perovskite nanocrystals.
[0530] (3) PQDs@PLGA perovskite nanocrystals were separated and purified by centrifugation at 10,000 r / min for 20 min. The obtained precipitate was dried in an oven at 60° C. for 1 h to obtain a light yellow powder, which turned green under ultraviolet light.
[0531] (4) The powder was dispersed in water and the hydrophobic PQDs@PLGA perovskite nanocrystals were stored at room temperature.
[0532] Fig. 22 is a transmission electron microscopy image of the hydrophobic PQDs@PLGA perovskite nanocrystals prepared in Example 13. Fig. 22It can be seen that the average particle size of PQDs@PLGA perovskite nanocrystals is 80 nm, which is larger than that of Preparation Example 13, indicating that the carboxyl-terminated polylactic acid-glycolic acid copolymer encapsulates multiple PQDs quantum dots into an overall morphology, and the encapsulation effect is good.
[0533] Fig.23 This is an optical microscope image of the PQDs@PLGA perovskite nanocrystal of Example 13. The left image represents the fluorescence imaging image of the nanocrystal under 420-450nm excitation, and the right image represents the bright field image of the nanocrystal.
[0534] Fig.24 Fluorescence emission spectra and absorption spectra of PQDs@PLGA perovskite nanocrystals placed in water for at least 90 days. Fig.24 It can be seen that the PL spectrum of PQDs@PLGA perovskite nanocrystals placed for at least 90 days is almost consistent with the emission peak position and half-peak width of pure perovskite quantum dots PQDs. Although the absorption spectrum intensity is reduced due to a layer of polymer coated on its outer layer, it is also because of this that PQDs@PLGA perovskite nanocrystals can exist stably in the aqueous phase and almost retain the optical properties of PQDs quantum dots, and the coated particle size is uniform.
[0535] Example 23 Preparation of hydrophobic perovskite nanocrystal bio-nanoprobes by coupling method
[0536] In order to further couple the hydrophobic perovskite nanocrystals with biomaterials to construct a new type of nanobiological probe, based on Example 1, the surface groups of the encapsulation coating material polylactic acid were used, and EDC / NHS was used as a crosslinking agent to couple with biomaterials to construct a new type of fluorescent detection probe. The specific implementation steps are as follows:
[0537] (1) Prepare 6 mg / mL of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and 30 mg / mL of N-hydroxysuccinimide (NHS) in a 1:1 volume ratio for the cross-linking reaction.
[0538] (2) 10 mg of PQDs@PLGA perovskite nanocrystals were added to a mixed solution of 2 mL of EDC and NHS and stirred at room temperature and 300 r / min for 30 min to fully activate the -COOH on the surface of the PQDs@PLGA perovskite nanocrystals.
[0539] (3) Take 10 μL of human IgG antibody (1 mg / mL) and 4 μL of Triton X-100 and add them to the above solution (2), and react gently on a shaker for 30 minutes to obtain the PQDs@PLGA labeled human IgG probe PQDs@PLGA@IgG.
[0540] Fig.25The SEM image and EDS spectrum of the PQDs@PLGA perovskite nanocrystal coupled with human IgG antibody to form the bio-nanoprobe PQDs@PLGA@IgG in Example 23. As can be seen from the figure, the average particle size of the bio-nanoprobe PQDs@PLGA@IgG is 200nm; the polymer encapsulated perovskite quantum dots are successfully coupled with the antibody protein, and the EDS spectrum further proves the presence of the main elements Pb, Cs, and Br that form the perovskite quantum dots.
[0541] Example 33 Nanoprobes Recognize Antigens
[0542] After the construction of the biological nanoprobe is completed, the recognition function of the probe is verified. On the basis of Example 23, the conventional experimental method in biological experiments is used to verify the recognition function of the probe. This example uses the nanoprobe PQDs@PLGA labeled human IgG prepared in Example 23 as an antibody, and the target analyte is Eu-labeled anti-human IgG as an antigen. Fig. 27 This is a schematic diagram of the experiment for the recognition and verification of the bio-nanoprobe PQDs@PLGA@IgG and Eu-labeled anti-human IgG in this example.
[0543] (1) A 96-well plate was used to coat the bottom of the plate. Eu-labeled anti-human IgG (10 μg / mL) was coated at a dosage of 50 μL / well and set as the experimental group, and incubated overnight at 4°C. At this time, a control experimental group was set, and the bottom of the plate was coated with other substances, a control group with bovine serum albumin (BSA) coated and incubated, and a blank group with a complete blank control.
[0544] The coated 96-well plate was taken out, and the incubation well plates of the experimental group, control group, and blank group were washed 3 to 5 times with PBST (PBS buffer, pH = 7.3, containing 0.5 volume concentration of Tween-20) to wash away the excess uncoated Eu-labeled anti-human IgG or BSA.
[0545] (2) The coated well plate was sealed by preparing 5% skim milk powder at a dosage of 200 μL / well and incubating the well plate at 37°C for 1 h to occupy the sites of the coated antibody at the bottom of the plate and reduce nonspecific adsorption; the sealed well plate was washed 3 to 5 times with PBST (PBS buffer, pH = 7.3, containing 0.5 ppm by volume of Tween-20) to wash away the excess skim milk powder solution.
[0546] (3) Add 100 μL of the bio-nanoprobe PQDs@PLGA@IgG prepared in Example 33 to the 96-well plate coated with Eu-labeled anti-human IgG and bovine serum albumin BSA after blocking, and incubate at 37°C for 1 h; wash the identification plate 3 to 5 times with PBST (PBS buffer, pH = 7.3, containing 0.5 ppm by volume of Tween-20) to wash away excess unrecognized PQDs@PLGA@IgG.
[0547] Fig.26 This is the Confocal fluorescence imaging of the PQDs@PLGA perovskite nanocrystals in Example 33 coupled with human IgG antibodies to form the bio-nanoprobe PQDs@PLGA@IgG, and verified by Eu-labeled anti-human IgG recognition, with dual-channel 488nm and 561nm excitation.
[0548] Among them, the first row is the experimental group, the plate is coated with Eu labeled anti-human IgG, the corresponding pictures are numbered 1 to 3, PQDs@PLGA labeled human IgG recognition, red fluorescence is presented in the 561nm excitation channel (i.e., picture number 3), and green fluorescence is presented in the 488nm excitation channel (i.e., picture number 2); Merge represents 488nm and 561nm dual channel excitation, showing superimposed yellow fluorescence imaging of red and green fluorescence (i.e., picture number 1). The second row is the bovine serum albumin control group, the plate is coated with bovine serum albumin, and PQDs@PLGA labeled human IgG recognition is added, the corresponding pictures are numbered 4 to 6; the third row is the blank group (Blank), the plate is not coated with antigen, PQDs@PLGA labeled human IgG recognition is added, the corresponding pictures are numbered 7 to 9.
[0549] from Fig.26 It can be seen from the fluorescence imaging that the experimental group showed a red fluorescence image under 561nm excitation light because the bottom of the plate was coated with Eu-labeled anti-human IgG, and the recognized human IgG showed green fluorescence imaging under 488nm excitation conditions when labeled with PQDs@PLGA, which can prove that the antibody-antigen recognition is successful; at the same time, the control group used antigens that cannot recognize each other instead and the blank group, which showed no red fluorescence image and green fluorescence image respectively, further proving that the biological nanoprobe is not only successfully coupled, but also retains the original recognition function.
[0550] The biomaterial in the above embodiment can also be replaced by an aptamer or a polypeptide to obtain a nanoprobe in which the perovskite nanocrystal is coupled with the aptamer or the polypeptide. The obtained nanoprobe also has a specific recognition function.
Claims
1. Use of perovskite nanocrystals in preparing probes for tumor diagnosis or treatment, characterized in that: The perovskite nanocrystals include perovskite quantum dots and liposome materials coated on the surface of the perovskite quantum dots; the perovskite quantum dots are CsPbBr3 perovskite quantum dots; the liposome material is a carboxyl-terminated polylactic acid-glycolic acid copolymer; the number average molecular weight of the carboxyl-terminated polylactic acid-glycolic acid copolymer is 100-200000, and the carboxyl-terminated polylactic acid-glycolic acid copolymer is randomly copolymerized by racemic lactide and glycolide, and the ratio of racemic lactide to glycolide is (50-90):(10-50); the probe is a biomaterial labeled with perovskite nanocrystals; the biomaterial is chlorotoxin; the tumor is a brain glioma; the mass ratio of the perovskite quantum dots to the liposome material is 116:(25-50); the average particle size of the perovskite nanocrystals is 5-100 nm; the steps of coating the carboxyl-terminated polylactic acid-glycolic acid copolymer onto the surface of the perovskite quantum dot to form perovskite nanocrystals are as follows: (1) dissolving 0.2 mmol CsBr, 0.2 mmol PbBr2 and 90 mg of carboxyl-terminated polylactic acid-glycolic acid copolymer in 5 mL of N,N-dimethyl diamide solvent, and after complete dissolution, adding 0.5 mL of oleic acid and 0.25 mL of oleylamine to stabilize the solution; (2) taking 0.5 mL of the mixed solution obtained in step (1) and adding it dropwise to 10 mL of vigorously stirred toluene solution to obtain CsPbBr3-QDs@PLGA quantum dot solution; (3) taking 1 mL of the solution obtained in step (2) and adding it to 15 mL of toluene solution. , stirring the reaction for 48 hours to ensure complete coating, and obtaining a CsPbBr3-QDs@PLGA perovskite nanocrystal mixed solution; (4) centrifuging the CsPbBr3-QDs@PLGA perovskite nanocrystal mixed solution obtained in step (3) at 10000r for 10 minutes, and drying the obtained precipitate in an oven at 60°C for 1 hour; (5) adding 2-4 mL of water to the dried product in step (4), and ultrasonicating for 2 minutes to obtain a uniformly dispersed CsPbBr3-QDs@PLGA perovskite nanocrystal dispersion.
2. The use according to claim 1, characterized in that: The spectral range of the water-soluble perovskite nanocrystal is 470-650 nm.
Citation Information
Patent Citations
Double-mode imaging and medicine-loading integrated nano medicine carrier and preparation method thereof
CN102552946A
Method for preparing dual-function targeting quantum dot lipidosome
CN102973510A
Preparation method and application of targeted co-supported drug delivery system nano-particles based on polylactic-co-glycolic acid
CN103623430A
Novel fluorescence lipidosome nano probe and preparing method thereof
CN105535996A
Targeting fluorescent-magnetic nano-material as well as preparation method and application thereof
CN106563134A
